Electronic component
By designing a linear adhesive sheet with multiple ends, the problems of large and residual adhesion during peeling of existing adhesive tapes are solved, and rapid and complete peeling and reduced labor consumption are achieved.
Patent Information
- Application Number
- CN202411634077.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-04
- Filing Date
- 2020-01-23
- Publication Date
- 2025-02-14
AI Technical Summary
The existing adhesive tape has a high adhesive force during peeling, resulting in high labor consumption and easy to leave adhesive residue, affecting reuse and reuse.
Design an adhesive sheet with the surface of which is attached to the adhesive in a straight form in a manner that at least a portion is attached to the adhesive and is attached in a state where at least two ends are exposed from the second adhesive sheet to ensure that the adhesive sheet is peeled off can be stretched quickly and peeled completely.
The rapid peeling of the adhesive sheet is achieved, preventing adhesive residues, and can continue peeling from the other end to the end even in the case of mid-break, reducing labor consumption and promoting reuse and reuse.
Smart Images

Figure CN119432239A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of January 23, 2020, Chinese application number 202080010240.3, and invention name “Electronic Components”. Technical Field
[0002] The present invention relates to electronic components. Background Art
[0003] In the case of fixing components constituting electronic devices, adhesive sheets (sometimes also referred to as "adhesive tapes") are widely used as a bonding means with excellent workability and high bonding reliability. Specifically, adhesive tapes are used for fixing metal plates constituting relatively large electronic devices such as thin-film televisions, home appliances, and OA equipment, fixing exterior components to frames, fixing rigid components such as exterior components and batteries to relatively small electronic devices such as portable electronic terminals, cameras, and personal computers, etc., for temporary fixing of the components, and for labeling of product information.
[0004] In recent years, in the above-mentioned industrial fields, from the perspective of protecting the global environment, for the purpose of saving resources, etc., the situation of reusing or reusing parts used in products by disassembling them after use and reusing or reusing them is increasing. At this time, when using an adhesive tape, it is necessary to peel off the adhesive tape attached to the parts, but the above-mentioned adhesive tape usually has a strong adhesive force and is attached to multiple parts of the product, so the operation of peeling them off is accompanied by considerable labor. Therefore, when the above-mentioned reuse or reuse is required, it is required to reduce the operating cost by easy peeling and removal.
[0005] As an adhesive tape that can be easily peeled and removed, an adhesive tape is proposed, which has an adhesive portion and a tab portion, the tab portion is attached in a manner that extends from one of the extension portions of the first adherend and the extension portion of the second adherend and can be clamped, and the tab portion can be clamped and stretched in a direction roughly parallel to the adhesive surface to be peeled off (refer to patent document 1). However, as in the proposed adhesive tape, when the tab portion (holding portion) used for elongation and peeling only exists at one end, there is a problem that the adhesive remains on the adherend after the adhesive tape is peeled off, causing contamination on the adhesive surface of the adhesive tape on the opposite side of the side having the tab portion (that is, the surface that the adhesive tape is adhered to for the longest time during peeling). In addition, there is also the following problem: in the case of a rupture in the middle of the elongation and peeling of the tab portion from one end, it is impossible to peel it off further, and it is impossible to further disassemble the components that can be reused or re-used.
[0006] In contrast, a method such as Figure 1The adhesive film shown includes an adhesive region (2) adjacent to a handle tab (1) located at one end of the adhesive film sheet and extending toward another end (3), wherein the adhesive region (2) includes, in order from the handle tab (1) toward the other end (3) of the adhesive film sheet: a first adhesive region (4) having a larger cross-sectional area than the second adhesive region (5); a second adhesive region (5) having a cross-sectional area that decreases sharply toward the end (3); and a third adhesive region (6) forming the end (3) and terminating at one or more front end portions (7) in the direction toward the end (3) (see patent document 2). However, in the case of the shape of the adhesive film of the proposal, there are problems such as a reduced attachment area, inability to effectively utilize the attachable area, and weakened adhesive force. In the above-mentioned electronic device, it is a big problem that the components constituting the electronic device are peeled off during use, and in order to be able to reuse or re-use, it is necessary to maintain the adhesive force before the electronic components are recovered.
[0007] Therefore, there is a strong demand for an electronic component having an adhesive sheet that can be quickly peeled off, has no contamination caused by the adhesive after peeling, can be peeled off from the other end to the end even if the adhesive sheet is broken during peeling from one end, and has suitable adhesive strength when used.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2015-124289
[0011] Patent Document 2: U.S. Patent No. 6,680,096 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The present invention aims to solve the above-mentioned various problems in the past and achieve the following objectives. That is, the present invention aims to provide an electronic component having an adhesive sheet that can be quickly peeled off, has no contamination caused by the adhesive after peeling off, can be peeled off from the other end to the end even if the adhesive sheet is broken during the peeling from one end, and has suitable adhesive force when used.
[0014] Means for solving problems
[0015] Means for solving the above-mentioned problems are as follows.
[0016] That is, an electronic component is characterized in that it has an adhesive sheet, one surface of which is attached to a first attachment object in a manner in which at least a portion of the surface is linear, and the other surface is attached to a second attachment object, and is attached to the second attachment object in a state in which at least two ends are exposed from the second attachment object.
[0017] Effects of the Invention
[0018] According to the present invention, the above-mentioned various problems in the past can be solved, the above-mentioned objectives can be achieved, and an electronic component can be provided, which has an adhesive sheet that can be quickly peeled off, has no contamination caused by the adhesive after peeling off, and even if the adhesive sheet is broken in the middle of being stretched and peeled off from one end, it can be stretched and peeled off from the other end to the end, and has suitable adhesive force when used. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a figure which shows the adhesive film of a prior art.
[0020] Figure 2A This is a schematic explanatory diagram (plan view) showing one embodiment of the electronic component of the present invention.
[0021] Figure 2B This is a schematic explanatory diagram (cross-sectional view) showing one embodiment of the electronic component of the present invention.
[0022] Figure 2C This is a schematic explanatory diagram (cross-sectional view) showing another embodiment of the electronic component of the present invention.
[0023] Figure 2D This is a schematic explanatory diagram (plan view) showing another embodiment of the electronic component of the present invention.
[0024] Figure 2E This is a schematic explanatory diagram (plan view) showing another embodiment of the electronic component of the present invention.
[0025] Figure 2F This is a schematic explanatory diagram (plan view) showing another embodiment of the electronic component of the present invention.
[0026] Figure 2G This is a schematic explanatory diagram (plan view) showing another embodiment of the electronic component of the present invention.
[0027] Figure 3A This is a schematic explanatory diagram (cross-sectional view) when the electronic component of the present invention is a battery.
[0028] Figure 3B This is a schematic diagram (top view) of the electronic component of the present invention when it is a battery.
[0029] Figure 3CThis is a schematic explanatory diagram (cross-sectional view) showing another embodiment in which the electronic component of the present invention is a battery.
[0030] Figure 4A This is a schematic explanatory diagram (cross-sectional view) in the case where the electronic component of the present invention is a display of a television.
[0031] Figure 4B This is a schematic explanatory diagram (top view) of a case where the electronic component of the present invention is a display of a television.
[0032] Figure 5A This is a schematic explanatory diagram (cross-sectional view) of a method of attaching a pressure-sensitive adhesive sheet 31 to an acrylic plate 32 when evaluating impact resistance in Examples.
[0033] Figure 5B This is a schematic explanatory diagram (top view) of a test piece prepared when evaluating impact resistance in Examples.
[0034] Figure 5C This is a schematic explanatory diagram (cross-sectional view) regarding a method of setting a test piece on a U-shaped measuring table when evaluating impact resistance in Examples.
[0035] Fig. 6A It is a schematic explanatory diagram (cross-sectional view) of the attachment form X in Test Examples 1 to 11 and the stretching direction (horizontal direction) in the stretch peel test.
[0036] Figure 6B It is a schematic explanatory diagram (cross-sectional view) of the attachment form X in Test Examples 1 to 11 and the stretching direction (vertical direction) in the stretch peel test.
[0037] Figure 6C This is a schematic explanatory diagram (cross-sectional view) comparing the attachment method Y in Test Examples 1 to 11 and the stretching direction (horizontal direction) in the stretch peeling test.
[0038] Fig. 7A It is a figure which shows the external appearance of the acrylic plate after being stretched and peeled in the horizontal direction in Test Example 1 (attachment form X).
[0039] Figure 7B It is a figure which shows the external appearance of the acrylic plate after being stretched and peeled in the horizontal direction in Test Example 1 (attaching method Y). DETAILED DESCRIPTION
[0040] (Electronic Components)
[0041] The electronic component comprises an adhesive sheet, one surface of the adhesive sheet is attached to a first attachment object in a manner that at least a portion of the adhesive sheet is linear, and the other surface of the adhesive sheet is attached to a second attachment object, and is attached to the second attachment object in a state where at least two ends are exposed from the second attachment object. It should be noted that in this specification, the first attachment object or the second attachment object is sometimes collectively referred to as an "adherend".
[0042] In this specification, the above-mentioned electronic components include not only the various components such as metal plates, exteriors, frames, batteries, etc. that constitute the above-mentioned electronic devices, but also the electronic devices themselves such as televisions, home appliances, OA equipment, portable electronic terminals, cameras, personal computers, etc.
[0043] Hereinafter, the configuration of the electronic component will be described in detail using the drawings, but the present invention is not limited to these embodiments.
[0044] like Figure 2A and Figure 2B As shown, in the electronic component, one surface 21a of the adhesive sheet 21 is attached to one surface of the first attachment object 22 constituting the electronic component in a manner that at least a portion thereof becomes linear. Next, the other surface 21b of the adhesive sheet 21 is attached to the second attachment object 23 constituting the electronic component. At this time, the two ends of the adhesive sheet 21 in the longitudinal direction are attached in a state of being exposed from the second attachment object 23. Thus, at least a portion of each end of the adhesive sheet 21 exposed from the second attachment object 23 functions as a gripping portion. Figure 2C It is a diagram showing another embodiment of the electronic component.
[0045] In the above Figure 2A to Figure 2C In the example in which the adhesive sheet is attached to the attachment object in a linear manner and the end portion of the adhesive sheet is two, the adhesive sheet only needs to be attached to the first attachment object in a linear manner with at least a portion of its surface, such as Figure 2D to Figure 2G As shown, the above-mentioned adhesive sheet can also be attached to the above-mentioned first attachment object in a shape that branches midway or bends midway. Therefore, the number of the ends (holding portions) of the above-mentioned adhesive sheet is not particularly limited, and can be appropriately selected according to the attachment shape of the above-mentioned adhesive sheet. At this time, as the number of the ends of the above-mentioned adhesive sheet exposed from the above-mentioned second attachment object, there is no particular restriction as long as it is at least 2, and it can be appropriately selected according to the purpose, and preferably all the ends are exposed from the above-mentioned second attachment object. Hereinafter, each end of the adhesive sheet 21 exposed from the second attachment object 23 is sometimes referred to as the first holding portion A, the second holding portion B, the third holding portion C, the fourth holding portion D, etc.
[0046] exist Figure 2A to Figure 2G, an example is shown in which each holding part A~D is not exposed from the first attachment object 22, but there is no particular limitation as long as at least two of the holding parts A~D are exposed from the second attachment object 23, and at least any one of the holding parts A~D can be exposed from the first attachment object 22.
[0047] <Handle section>
[0048] The above-mentioned holding part can be as follows Figure 2A and Figure 2B As shown in the figure, it can be directly arranged on the first attachment object 22, or it can be arranged as shown in the figure. Figure 2C As shown in FIG. 1 , the second attachment object 23 is arranged on the side surface (surface in the thickness direction) ( Figure 2A to Figure 2C Although not shown in the figure, the first holding part A and the second holding part B) in the figure can also be configured to contact other elements of the above-mentioned electronic components adjacent to at least one of the first attachment object 22 and the second attachment object 23.
[0049] The holding portion is the end of the adhesive sheet, and the number of adhesive layers in the adhesive surface with at least any one of the first attachment object and the second attachment object may be the same as or different from the number of adhesive layers in the holding portion. For example, in the case where the adhesive sheet has adhesive layers on both sides, the adhesive layer in at least any one of the plurality of holding portions may be disposed only on one side. In addition, the number of adhesive layers in the plurality of holding portions may be the same as or different from each other.
[0050] In addition, the holding portion may be formed by processing at least a portion of the end of the adhesive sheet. The processing is not particularly limited and can be appropriately selected according to the purpose, for example, the processing of removing the adhesive layer in the adhesive sheet, the processing of configuring a release sheet on the surface of the adhesive layer in the adhesive sheet, and the processing of modifying the adhesive layer in the adhesive sheet to be non-adhesive by known means such as a release agent.
[0051] The release sheet is not particularly limited and can be appropriately selected according to the purpose, for example, kraft paper, glassine paper, woodfree paper, etc.; resin films such as polyethylene, polypropylene (biaxially stretched polypropylene (OPP), uniaxially stretched polypropylene (CPP)), polyethylene terephthalate (PET), etc.; laminated paper formed by laminating the above paper with a resin film, paper formed by applying a release treatment such as silicone resin to one or both sides of the paper subjected to a gap filling treatment with clay, polyvinyl alcohol, etc., etc. These can be used alone or in combination of two or more.
[0052] The length of the holding portion is not particularly limited as long as it is a length that can be stretched, and can be appropriately selected based on the spacing between other electronic components adjacent to the first attachment object and the second attachment object, and is preferably 5 mm or more, more preferably 10 mm or more, and further preferably 15 mm or more. The upper limit of the length is not particularly limited, and can be appropriately selected based on the size of the electronic component, and is preferably 20 mm or less.
[0053] The lengths of the above-mentioned holding parts may be the same or different.
[0054] The width of the holding portion is not particularly limited and may be appropriately selected according to the width of the pressure-sensitive adhesive sheet and the like.
[0055] <Stretching direction p>
[0056] The adhesive sheet 21 in the electronic component is Figure 2B and Figure 2C The film is easily peeled by stretching in the stretching direction p shown. Figure 2B The stretching direction p of the adhesive sheet 21 is shown to be horizontal (180° direction) with respect to the attachment surfaces of the first attachment object 22 and the second attachment object 23. Figure 2C The stretching direction p of the adhesive sheet 21 is shown to be perpendicular (90° direction) to the attachment surfaces of the first attachment object 22 and the second attachment object 23. There is no particular restriction on the angle of the stretching direction p relative to the attachment surfaces of the first attachment object 22 and the second attachment object 23, and it can be appropriately selected according to the surrounding environment of the electronic component, etc.
[0057] The adhesive sheet in the electronic component can be peeled off by simultaneously stretching the plurality of gripping parts, or after a portion of the adhesive sheet is peeled off by stretching any one of the plurality of gripping parts, the remaining portion can be peeled off by stretching another one. In addition, since at least two ends of the adhesive sheet in the electronic component are exposed from the second attachment object, even if the adhesive sheet is broken during the stretching and peeling from one end (the first gripping part), it can be stretched and peeled from the other end (the second gripping part) to the end, which is advantageous.
[0058] The removability of the adhesive sheet in the electronic component can be confirmed, for example, by the method described in <<Evaluation 1 of Removability>> in the test examples described later. In the evaluation of removability, the sheet having no contamination caused by the adhesive after peeling and being able to be peeled off from the other end of the gripping portion to the end even if it is broken during the peeling from the gripping portion at one end is considered to have excellent removability.
[0059] <Attachment area width / Attachment area length (X / Y)>
[0060] When the width of the attachment area of the adhesive sheet in the electronic component is X (cm) and the length of the attachment area is Y (cm), the ratio of the width of the attachment area to the length of the attachment area represented by [X / Y] is not particularly limited and can be appropriately selected according to the purpose, preferably 1 / 1 to 1 / 100000, more preferably 1 / 1 to 1 / 10000, and further preferably 1 / 1 to 1 / 1000. If the ratio of the attachment area is less than 1 / 1, the adhesive force may become insufficient, and if it exceeds 1 / 100000, the adhesive sheet may be broken during the stretching and peeling, or contamination caused by the adhesive may occur after peeling.
[0061] <First attachment target or second attachment target>
[0062] The first attachment object and the second attachment object may be the same component or different components. In addition, the first attachment object and the second attachment object may be exchanged.
[0063] The materials of the first attachment object and the second attachment object are not particularly limited and can be appropriately selected according to the type of electronic components, such as metal, alloy, glass, plastic, ceramic, etc. These materials can be used alone or in combination of two or more.
[0064] Specific examples of the first attachment object include a rear chassis, a frame, a metal plate, a frame, a heat sink, and the like.
[0065] Specific examples of the second attachment object include display glass, batteries, heat sinks and other heat dissipation members, speakers, camera lenses, and the like.
[0066] Among them, it is preferred that the first attached object and the second attached object are recycling parts. The recycling parts are not particularly limited as long as they can be reused or re-used, and can be appropriately selected according to the purpose, for example, recycling parts when bad conditions occur in the manufacturing process of electronic components, recycling parts when discarded, etc. The adhesive sheet in the electronic component can be quickly peeled off, and there is no contamination caused by the adhesive after peeling. Even if it breaks in the middle of the peeling from one end, it can be peeled from the other end to the end. Therefore, at least any one of the first attached object and the second attached object as the recycling part can be quickly recovered, and there is no contamination when at least any one of the first attached object and the second attached object is reused or re-used, which is advantageous.
[0067] Hereinafter, more specific embodiments of the electronic component will be described with reference to the drawings, but the present invention is not limited to these embodiments.
[0068] Hereinafter, an embodiment in which the electronic component is a small component such as a battery will be described in detail.
[0069] like Figure 3A and Figure 3B As shown, one surface 61a of the adhesive sheet 61 is attached to the fixing portion of the battery 63 of the rear base 62 in a manner that at least a portion thereof becomes linear. Next, the other surface 61b of the adhesive sheet 61 is attached to the battery 63. At this time, the two ends (the first gripping portion A and the second gripping portion B) of the adhesive sheet 61 in the length direction (extension direction) are attached in a state where they are exposed from both ends of the battery 63. In addition, the first gripping portion A and the second gripping portion B on the adhesive sheet 61 may also be attached in a manner that Figure 3C The method shown.
[0070] In addition, an embodiment in which the electronic component is a large component such as a display of a television set will be specifically described below.
[0071] like Figure 4A and Figure 4B As shown, one surface of the adhesive sheet 71 is attached to the fixing portion of the display 73 of the frame 72 in a manner that at least a portion thereof becomes linear. Next, the other surface of the adhesive sheet 71 is attached to the display 73. At this time, the two ends (the first gripping portion A and the second gripping portion B) of the adhesive sheet 71 in the length direction (extension direction) are attached in a state where they are exposed from both ends of the display 73, respectively.
[0072] <Adhesive Sheet>
[0073] The pressure-sensitive adhesive sheet has at least a pressure-sensitive adhesive layer, preferably a base layer, and further has other layers as necessary.
[0074] It is preferred that at least one of the one surface and the other surface of the pressure-sensitive adhesive sheet include the pressure-sensitive adhesive layer, and it is more preferred that both of the one surface and the other surface of the pressure-sensitive adhesive sheet include the pressure-sensitive adhesive layer.
[0075] <<Adhesive layer>>
[0076] The adhesive layer contains at least an adhesive composition and further contains other components as necessary.
[0077] - Adhesive composition -
[0078] The adhesive composition contains at least the adhesive resin and further contains other components as necessary.
[0079] As the above-mentioned binder resin, there is no particular limitation and it can be appropriately selected from known substances, for example, acrylic binder resin, rubber binder resin, urethane binder resin, silicone binder resin, etc. can be mentioned. They can be used alone or in combination of two or more. Among them, as the above-mentioned binder resin, acrylic binder resin is preferred.
[0080] --Acrylic Binder Resin--
[0081] The acrylic binder resin is not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include resins containing an acrylic polymer and, if necessary, additives such as a tackifier resin and a crosslinking agent.
[0082] The acrylic polymer can be produced, for example, by polymerizing a monomer mixture containing a (meth)acrylic monomer.
[0083] As the (meth)acrylic monomer, for example, an alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms, etc. can be used.
[0084] Specific examples of the alkyl (meth)acrylate having an alkyl group with 1 to 12 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0085] As the alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms, an alkyl (meth)acrylate having an alkyl group having 4 to 12 carbon atoms is preferably used, and an alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms is more preferably used. In terms of ensuring excellent adhesion to the adherend, n-butyl acrylate is particularly preferably used.
[0086] The alkyl (meth)acrylate having an alkyl group having 1 to 12 carbon atoms is preferably used in an amount of 80 to 98.5 wt %, more preferably 90 to 98.5 wt %, based on the total amount of monomers used in the production of the acrylic polymer.
[0087] As monomers that can be used for producing the acrylic polymer, in addition to the above-mentioned monomers, high-polarity vinyl monomers can be used as needed.
[0088] Examples of the highly polar vinyl monomer include (meth)acrylic monomers having a hydroxyl group, (meth)acrylic monomers having a carboxyl group, (meth)acrylic monomers having an amide group, and the like, and sulfonic acid group-containing monomers such as vinyl acetate, ethylene oxide-modified succinic acid acrylate, and 2-acrylamide-2-methylpropanesulfonic acid. These monomers may be used alone or in combination of two or more.
[0089] Specific examples of the vinyl monomer having a hydroxyl group include (meth)acrylic monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.
[0090] The vinyl monomer having a hydroxyl group is preferably used when a binder resin containing an isocyanate crosslinking agent is used as the binder resin. Specifically, as the vinyl monomer having a hydroxyl group, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate are preferably used.
[0091] The vinyl monomer having a hydroxyl group is preferably used in an amount within a range of 0.01 to 1.0 wt %, more preferably 0.03 to 0.3 wt %, based on the total amount of monomers used in the production of the acrylic polymer.
[0092] Specific examples of the vinyl monomer having a carboxyl group include (meth)acrylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, (meth)acrylic acid dimer, crotonic acid, and ethylene oxide-modified succinic acid acrylate. Among them, acrylic acid is preferred.
[0093] Specific examples of the vinyl monomer having an amide group include (meth)acrylic monomers such as N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, and N,N-dimethylacrylamide.
[0094] The above-mentioned high-polarity vinyl monomer is preferably used in the range of 1.5 wt % to 20 wt %, more preferably in the range of 1.5 wt % to 10 wt %, relative to the total amount of monomers used in the production of the above-mentioned acrylic polymer. When used in the range of 2 wt % to 8 wt %, an adhesive layer having a balance in cohesion, holding power and adhesion can be formed, and therefore it is further preferred.
[0095] There are no particular restrictions on the method for producing the acrylic polymer, and it can be appropriately selected from known methods according to the purpose, for example, a method of polymerizing the monomers by a polymerization method such as solution polymerization, bulk polymerization, suspension polymerization, emulsion polymerization, etc. Among them, the acrylic polymer is preferably produced by solution polymerization or bulk polymerization.
[0096] In the above-mentioned polymerization, peroxide-based thermal polymerization initiators such as benzoyl peroxide and lauroyl peroxide, azo thermal polymerization initiators such as azobisisobutyronitrile, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, benzyl ketal-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzophenone-based photopolymerization initiators, etc. can be used as needed.
[0097] The acrylic polymer obtained by the above method preferably has a weight average molecular weight of 300,000 to 3,000,000, and more preferably 500,000 to 2,500,000, as measured by gel permeation chromatography (GPC) in terms of standard polystyrene.
[0098] Here, the weight average molecular weight of the acrylic polymer measured by the GPC method is a standard polystyrene conversion value measured using a GPC apparatus (HLC-8329GPC, manufactured by Tosoh Corporation), and the measurement conditions are as follows.
[0099] [Measurement conditions]
[0100] Sample concentration: 0.5 wt% (tetrahydrofuran (THF) solution)
[0101] Sample injection volume: 100μL
[0102] Eluent: THF
[0103] Flow rate: 1.0mL / min
[0104] ·Measurement temperature: 40℃
[0105] ·This column: TSKgel GMHHR-H (20) 2 pieces
[0106] Guard column: TSKgel HXL-H
[0107] Detector: Differential refractometer
[0108] · Standard polystyrene molecular weight: 10,000 to 20,000,000 (manufactured by Tosoh Corporation)
[0109] As the acrylic adhesive resin, it is preferable to use an acrylic adhesive resin containing a tackifier resin in order to improve the adhesion to an adherend and the surface adhesive strength.
[0110] The tackifier resin contained in the acrylic adhesive resin is not particularly limited and can be appropriately selected according to the purpose. A tackifier resin having a softening point of 30°C to 180°C is preferred, and a tackifier resin having a softening point of 70°C to 140°C is more preferred from the perspective of forming an adhesive layer having high adhesive performance. It should be noted that when a (meth)acrylate tackifier resin is used, a tackifier resin having a glass transition temperature of 30°C to 200°C is preferred, and a tackifier resin having a glass transition temperature of 50°C to 160°C is more preferred.
[0111] As the specific example of the tackifier resin contained by the above-mentioned acrylic adhesive resin, rosin-based tackifier resin, polymerized rosin-based tackifier resin, polymerized rosin ester-based tackifier resin, rosin phenol-based tackifier resin, stabilized rosin ester-based tackifier resin, disproportionated rosin ester-based tackifier resin, hydrogenated rosin ester-based tackifier resin, terpene-based tackifier resin, terpene-phenol-based tackifier resin, petroleum resin-based tackifier resin, (methyl) acrylate-based tackifier resin, etc. can be enumerated. They can be used alone or in combination of more than two kinds. Wherein, the above-mentioned tackifier resin is preferably polymerized rosin ester-based tackifier resin, rosin phenol-based tackifier resin, disproportionated rosin ester-based tackifier resin, hydrogenated rosin ester-based tackifier resin, terpene-phenol-based resin, (methyl) acrylate-based resin.
[0112] The amount of the tackifier resin used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in a range of 5 to 65 parts by weight relative to 100 parts by weight of the acrylic polymer. When used in a range of 8 to 55 parts by weight, it is easier to ensure adhesion to the adherend, so it is more preferred.
[0113] As the acrylic adhesive resin, it is preferable to use an acrylic adhesive resin containing a crosslinking agent in order to further improve the cohesive force of the adhesive layer.
[0114] As the cross-linking agent, there is no particular limitation and it can be appropriately selected according to the purpose, for example, isocyanate cross-linking agents, epoxy cross-linking agents, metal chelate cross-linking agents, aziridine cross-linking agents, etc. can be mentioned. One of them can be used alone, or two or more can be used in combination. Among them, the cross-linking agent is preferably a cross-linking agent of the type that is mixed after the manufacture of the acrylic acid polymer to allow the cross-linking reaction to proceed, and more preferably an isocyanate cross-linking agent and an epoxy cross-linking agent that are rich in reactivity with the acrylic acid polymer are used.
[0115] As the above-mentioned isocyanate crosslinking agent, for example, toluene diisocyanate, triphenylmethane isocyanate, naphthalene-1,5-diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, trimethylolpropane-modified toluene diisocyanate, etc. can be mentioned. These can be used alone or in combination of two or more. Among them, toluene diisocyanate, which is a trifunctional polyisocyanate compound, and its trimethylolpropane adducts and triphenylmethane isocyanate are particularly preferred.
[0116] As an index of the degree of crosslinking, the value of the gel fraction obtained by measuring the insoluble components of the above-mentioned adhesive layer after immersing it in toluene for 24 hours is used. The above-mentioned gel fraction of the above-mentioned adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 10% by weight to 70% by weight, more preferably 25% by weight to 65% by weight, and further preferably 35% by weight to 60% by weight from the aspect of obtaining an adhesive layer with good cohesiveness and adhesion.
[0117] It should be noted that the gel fraction refers to a value measured by the following method. An adhesive composition containing the above-mentioned adhesive resin and the above-mentioned additives as required is applied to a release sheet in such a manner that the thickness after drying becomes 50 μm, dried at 100°C for 3 minutes, aged at 40°C for 2 days, and the resultant is cut into 50 mm squares to serve as a sample. Next, the weight (G1) of the above-mentioned sample before immersion in toluene is measured in advance, and the toluene-insoluble components of the sample after immersion in a toluene solution at 23°C for 24 hours are separated by filtering with a 300-mesh metal mesh, and the weight (G2) of the residue after drying at 110°C for 1 hour is measured, and the gel fraction is calculated according to the following formula (4). It should be noted that the weight (G3) of the conductive particles in the sample is calculated based on the weight (G1) of the sample and the composition of the adhesive composition.
[0118] Gel fraction (weight %) = (G2-G3) / (G1-G3)×100 Formula (4)
[0119] --Rubber-based adhesive resin--
[0120] The rubber-based binder resin is not particularly limited, and examples thereof include resins containing a rubber material generally used as a binder resin, such as a synthetic rubber-based binder resin and a natural rubber-based binder resin, and, if necessary, additives such as a tackifier resin.
[0121] As the above-mentioned rubber material, for example, block copolymers of polyaromatic vinyl compounds and conjugated diene compounds can be cited; styrene resins such as styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, styrene-butadiene-styrene copolymers, styrene-ethylene-butylene copolymers, and styrene-ethylene-propylene copolymers, etc. They can be used alone or in combination of two or more. Among them, the above-mentioned styrene resins are preferred, and when two or more of the above-mentioned styrene resins are used, excellent adhesive properties and holding power can be given to the above-mentioned adhesive sheet, so it is more preferred, and it is particularly preferred to use the above-mentioned styrene-isoprene copolymer in combination with styrene-isoprene-styrene copolymer.
[0122] The above-mentioned styrene resin can be, for example, a styrene resin of a single structure of a linear structure, a branched structure or a multi-branched structure, or a mixture of styrene resins of different structures. When the above-mentioned styrene resin rich in linear structure is used for the above-mentioned adhesive layer, it is possible to impart excellent bonding properties to the above-mentioned adhesive sheet. On the other hand, a resin having a branched structure or a multi-branched structure and having a styrene block at the molecular end can adopt a quasi-crosslinked structure, which can impart excellent cohesive force, and thus can impart high holding power. Therefore, the above-mentioned styrene resin is preferably used in a mixture according to the required characteristics.
[0123] As the above-mentioned styrene resin, it is preferred to use a styrene resin having a structural unit represented by the following chemical formula (1) in a range of 10% to 80% by weight relative to the total weight of the styrene resin, more preferably a styrene resin having a structural unit represented by the following chemical formula (1) in a range of 12% to 60% by weight, further preferably a styrene resin having a structural unit represented by the following chemical formula (1) in a range of 15% to 40% by weight, and particularly preferably a styrene resin having a structural unit represented by the following chemical formula (1) in a range of 17% to 35% by weight. Thus, excellent adhesiveness and heat resistance can be obtained.
[0124] [Chemical formula 1]
[0125]
[0126] When the styrene resin is used in combination with the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, the content of the styrene-isoprene copolymer is preferably 0% to 80% by weight, more preferably 0% to 77% by weight, further preferably 0% to 75% by weight, and particularly preferably 0% to 70% by weight, relative to the total weight of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer. If the content of the styrene-isoprene copolymer is within the preferred range, the adhesive sheet can have both excellent adhesive performance and thermal durability.
[0127] In addition, as the above-mentioned styrene-isoprene copolymer, it is preferred to use a styrene-isoprene copolymer with a weight average molecular weight of 10,000 to 800,000 measured in terms of standard polystyrene by gel permeation chromatography (GPC), more preferably a styrene-isoprene copolymer with a weight average molecular weight of 30,000 to 500,000, and further preferably a styrene-isoprene copolymer with a weight average molecular weight of 50,000 to 300,000. By making the weight average molecular weight of the above-mentioned styrene-isoprene copolymer within the above-mentioned preferred range, it is possible to ensure the compatibility during heating fluidity and solvent dilution, so that the above-mentioned adhesive sheet with good workability in the manufacturing process and heat durability can be obtained, so it is preferred.
[0128] Here, the weight average molecular weight of the styrene-isoprene copolymer measured by the GPC method is a standard polystyrene conversion value measured using a GPC apparatus (SC-8020, manufactured by Tosoh Corporation), and the measurement conditions are as follows.
[0129] [Measurement conditions]
[0130] Sample concentration: 0.5 wt% (tetrahydrofuran solution)
[0131] Sample injection volume: 100μL
[0132] ·Eluent: Tetrahydrofuran
[0133] Flow rate: 1.0mL / min
[0134] ·Measurement temperature: 40℃
[0135] Main column: TSKgel (registered trademark) GMHHR-H (20) 2 pieces
[0136] Guard column: TSKgel HXL-H
[0137] Detector: Differential refractometer
[0138] · Standard polystyrene molecular weight: 10,000 to 20,000,000 (manufactured by Tosoh Corporation)
[0139] The method for producing the styrene-isoprene copolymer is not particularly limited and may be appropriately selected from conventionally known production methods. Examples of the method include a method of stepwise polymerization of a styrene block and an isoprene block by an anionic living polymerization method.
[0140] There are no particular restrictions on the method for producing the styrene-isoprene-styrene copolymer, and it can be appropriately selected from conventionally known production methods, for example, a method of stepwise polymerizing a styrene block and an isoprene block by an anionic living polymerization method, a method of producing a block copolymer containing an active terminal having an activity and then reacting the block copolymer with a coupling agent to produce a coupled block copolymer, etc.
[0141] The method for producing the mixture of the above-mentioned styrene-isoprene copolymer and the above-mentioned styrene-isoprene-styrene copolymer is not particularly limited and can be appropriately selected from conventionally known production methods. For example, there can be mentioned a method of mixing the above-mentioned styrene-isoprene copolymer produced by the above-mentioned method with the above-mentioned styrene-isoprene-styrene copolymer.
[0142] In addition, as a method for producing a mixture of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, the mixture may be produced simultaneously in one polymerization step.
[0143] As a more specific method, by anionic living polymerization, first, styrene monomer is polymerized in a polymerization solvent using an anionic polymerization initiator to form a polystyrene block containing an active terminal having an activity. Second, isoprene is polymerized using the active terminal having an activity of the polystyrene block to obtain a styrene-isoprene diblock copolymer containing an active terminal having an activity. Third, a portion of the above-mentioned styrene-isoprene diblock copolymer containing an active terminal having an activity is reacted with a coupling agent to form a coupled styrene-isoprene-styrene block copolymer. Fourth, for the remaining portion of the above-mentioned styrene-isoprene diblock copolymer containing an active terminal having an activity, a polymerization terminator is used to inactivate the active terminal having an activity to form a styrene-isoprene diblock copolymer.
[0144] The tackifier resin contained in the rubber-based adhesive resin is not particularly limited and can be appropriately selected depending on the purpose, but preferably has a softening point of 80° C. or higher. This can provide the PSA sheet having excellent initial adhesiveness and thermal durability.
[0145] As the above-mentioned tackifying resin, a tackifying resin that is solid at room temperature (23° C.) is preferred. Specific examples thereof include petroleum resins such as C5-based petroleum resins, C9-based petroleum resins, C5-based / C9-based petroleum resins, alicyclic petroleum resins, polymerized rosin-based resins, terpene-based resins, rosin-based resins, terpene-phenolic resins, styrene resins, coumarone-indene resins, xylene resins, phenolic resins, etc. These can be used alone or in combination of two or more. Among them, as the above-mentioned tackifying resin, it is preferred to use the above-mentioned C5-based petroleum resin and polymerized rosin-based resin in combination from the perspective of achieving further excellent initial adhesion and thermal durability.
[0146] The petroleum resin is easily compatible with the structural unit represented by the chemical formula (1) constituting the styrene-based resin, and as a result, the initial adhesive force and thermal durability of the pressure-sensitive adhesive sheet can be further improved.
[0147] Examples of the C5 petroleum resin include ESCOREZ 1202, ESCOREZ 1304, and ESCOREZ 1401 (all manufactured by ExxonMobil Corporation), Wingtack 95 (manufactured by Goodyear Tire and Rubber Company), Quintone K100, Quintone R100, and Quintone F100 (all manufactured by Nippon ZEON Co., Ltd.), Piccotac 95, and Piccopale 100 (manufactured by Rika Hercules Co., Ltd.), and the like.
[0148] Examples of the C9 petroleum resin include Nisseki Neopolymer L-90, Nisseki Neopolymer 120, Nisseki Neopolymer 130, Nisseki Neopolymer 140, Nisseki Neopolymer 150, Nisseki Neopolymer 170S, Nisseki Neopolymer 160, Nisseki Neopolymer E-100, Nisseki Neopolymer E-130, Nisseki Neopolymer 130S, and Nisseki Neopolymer S (all manufactured by JX Nippon Mining and Energy Corporation), and Petcoal (registered trademark) (manufactured by Tosoh Corporation).
[0149] As the C5 / C9 petroleum resin, a copolymer of the C5 petroleum resin and the C9 petroleum resin can be used, for example, ESCOREZ 2101 (manufactured by ExxonMobil Corporation), Quintone G115 (manufactured by Nippon ZEON Co., Ltd.), Hercotac 1149 (manufactured by Rika Hercules Co., Ltd.) and the like can be used.
[0150] The alicyclic petroleum resin can be obtained by hydrogenating the C9 petroleum resin, and examples thereof include ESCOREZ 5300 (manufactured by ExxonMobil Corporation), Alcon P-100 (manufactured by Arakawa Chemical Industries, Ltd.), and Rigalite R101 (manufactured by Rika Hercules Co., Ltd.).
[0151] The amount of the tackifier resin used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 0% by weight to 100% by weight, more preferably in the range of 0% by weight to 70% by weight, further preferably in the range of 0% by weight to 50% by weight, and particularly preferably in the range of 0% by weight to 30% by weight, relative to the total amount of the components constituting the rubber-based adhesive resin. By using the tackifier resin within the preferred range, it is easy to improve the interface adhesion between the adhesive layer and the substrate layer while taking into account the excellent elongation at break and thermal durability of the adhesive sheet.
[0152] The amount of the tackifier resin having a softening point of 80° C. or higher used is not particularly limited and may be appropriately selected according to the purpose. It is preferably used in the range of 3% by weight to 100% by weight, more preferably in the range of 5% by weight to 80% by weight, relative to the total amount of the styrene-based resin. From the perspective of obtaining the adhesive sheet having both further excellent adhesion and excellent thermal durability, it is particularly preferably used in the range of 5% by weight to 80% by weight.
[0153] In order to obtain adhesion and initial adhesion in a constant temperature environment, a tackifier resin having a softening point of -5°C or lower may be used in combination with the tackifier resin having a softening point of 80°C or higher.
[0154] The tackifier resin having a softening point of -5°C or lower is not particularly limited and may be appropriately selected from the known tackifier resins according to the purpose. It is preferred to use a tackifier resin that is liquid at room temperature.
[0155] Specific examples of the tackifying resin having a softening point of -5°C or less include process oil, polyester, liquid rubber such as polybutene, etc. These can be used alone or in combination of two or more. Among them, the tackifying resin having a softening point of -5°C or less using polybutene is preferred from the perspective of exhibiting further excellent initial adhesion.
[0156] The tackifier resin having a softening point of -5°C or lower is preferably used in an amount within a range of 0% to 40% by weight, more preferably 0% to 30% by weight, based on the total amount of the tackifier resin.
[0157] In addition, the above-mentioned tackifying resin having a softening point below -5°C is preferably used in a range of 0 wt% to 40 wt% relative to the total amount of the above-mentioned styrene-based resin. When used in a range of 0 wt% to 30 wt%, the initial bonding force can be improved to achieve good bonding, and sufficient thermal durability can be obtained, so it is more preferred.
[0158] There is no particular restriction on the weight ratio of the tackifying resin having a softening point of 80°C or higher to the tackifying resin having a softening point of -5°C or lower, and it can be appropriately selected according to the purpose. It is preferably used in a range of 5 to 50 in which the weight ratio of the tackifying resin having a softening point of 80°C or higher to the tackifying resin having a softening point of -5°C or lower, as represented by [weight of tackifying resin having a softening point of 80°C or higher / weight of tackifying resin having a softening point of -5°C or lower]. From the perspective of obtaining the above-mentioned adhesive sheet having both excellent initial adhesion and excellent holding power, it is more preferably used in a range of 10 to 30.
[0159] The weight ratio of the styrene resin to the tackifying resin is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in a range of 0.5 to 10.0 as shown by [styrene resin / tackifying resin]. When used in a range of 0.6 to 9.0, the initial adhesive force can be improved and excellent thermal durability can be obtained, so it is more preferred. In addition, for example, from the perspective of preventing peeling (resistance to rebound) caused by the rebound force of the adhesive sheet when attached to the curved surface of the adherend, it is preferred that the weight ratio [styrene resin / tackifying resin] is greater than 1.
[0160] -Other ingredients-
[0161] As the above-mentioned other components in the above-mentioned adhesive composition, there is no particular restriction, and it can be appropriately selected within the scope of not damaging the characteristics of the above-mentioned adhesive sheet, for example, polymer components other than the above-mentioned adhesive resin, filler particles, crosslinking agents, anti-aging agents, ultraviolet absorbers, fillers, inhibitors, surface conditioners, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weathering stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, plasticizers, softeners, flame retardants, metal deactivators and other additives can be cited. They can be used alone or in combination of more than two. Wherein, preferably include the above-mentioned filler particles.
[0162] The content of the other components in the adhesive layer may be appropriately selected within a range that does not impair the properties of the adhesive sheet.
[0163] By making the adhesive layer contain the filler particles, the filler particles are exposed from the adhesive layer when the adhesive sheet is stretched, thereby reducing the bonding area between the adhesive layer and the adherend. Therefore, even if the adhesive sheet is stretched in a direction perpendicular to the attachment surface (adhesive surface) of the adherend, it can be easily stretched and peeled off, which is advantageous.
[0164] The type of the filler particles is not particularly limited and can be appropriately selected within a range that does not impair the effects of the present invention, and may be inorganic filler particles or organic filler particles. These may be used alone or in combination of two or more.
[0165] Specific examples of the inorganic filler particles include aluminum hydroxide, magnesium hydroxide, aluminum oxide, silicon oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, iron oxide, silicon carbide, boron nitride, aluminum nitride, titanium nitride, silicon nitride, titanium boride, carbon, nickel, copper, aluminum, titanium, gold, silver, zirconium hydroxide, basic magnesium carbonate, dolomite, hydrotalcite, calcium hydroxide, barium hydroxide, tin oxide, tin oxide hydrate, borax, zinc borate, zinc metaborate, barium metaborate, zinc carbonate, magnesium-calcium carbonate, calcium carbonate, barium carbonate, molybdenum oxide, oxygen Antimony, red phosphorus, mica, clay, kaolin, talc, zeolite, wollastonite, montmorillonite, silicon dioxide (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, ultrafine amorphous silica, etc.), potassium titanate, magnesium sulfate, sepiolite, xonotlite, aluminum borate, barium sulfate, barium titanate, zirconium oxide, zirconium oxide, cerium, tin, indium, carbon, sulfur, tellurium, cobalt, molybdenum, strontium, chromium, barium, lead, tin oxide, indium oxide, diamond, magnesium, platinum, zinc, manganese, stainless steel, antimony pentoxide, etc. Among them, aluminum hydroxide, nickel, etc. are preferred.
[0166] Furthermore, the inorganic filler may be one that has been surface-treated by silane coupling treatment, stearic acid treatment, or the like in order to improve dispersibility in the binder resin.
[0167] Specific examples of the above-mentioned organic filler particles include polystyrene fillers, benzoguanamine fillers, polyethylene fillers, polypropylene fillers, silicone fillers, urea-formalin fillers, styrene / methacrylic acid copolymers, fluorine fillers, acrylic fillers, polycarbonate fillers, polyurethane fillers, polyamide fillers, epoxy resin fillers, thermosetting resin hollow fillers, etc.
[0168] As the shape of the above-mentioned filler particles, there is no particular restriction, and it can be appropriately selected according to the purpose, and can be a regular shape or an irregular shape. As the specific example of the shape of the above-mentioned filler particles, polygonal, cubic, elliptical, spherical, needle-shaped, flat, flaky, etc. can be cited. The above-mentioned filler particles of these shapes can be used alone or in combination of more than two kinds. In addition, it can also be a material formed by the agglomeration of filler particles of these shapes. Wherein, as the shape of the above-mentioned filler particles, preferably elliptical, spherical, polygonal. If the above-mentioned filler particle shape is elliptical, spherical, polygonal and other shapes, then when the above-mentioned adhesive sheet is stretched, the above-mentioned adhesive layer slides well relative to the above-mentioned adherend, even if the stretching direction of the above-mentioned adhesive sheet is 90 ° direction relative to the attachment surface of the adherend, it can also be easily stretched and peeled.
[0169] As the particle size distribution (D 90 / D 10 ), which is not particularly limited and can be appropriately selected according to the purpose, is preferably 2.5 to 20, more preferably 2.5 to 15, and further preferably 2.5 to 5 from the perspective of impact resistance. 90 / D 10 ) is within the above preferred range, even if the stretching direction of the adhesive sheet is 90° relative to the attachment surface of the adherend, it can be easily stretched and peeled, and even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to break, and the impact resistance, shear adhesion and splitting adhesion are excellent. On the other hand, if the particle size distribution (D 90 / D 10 ) is less than 2.5, the elongation peeling property of the above-mentioned adhesive sheet when the elongation direction is 90° relative to the attachment surface of the adherend is sometimes impaired. If it exceeds 20, the adhesive properties such as impact resistance, shear adhesion, and cleavage adhesion are sometimes impaired.
[0170] The particle size distribution of the filler particles (D 90 / D 10) is obtained by, for example, measuring the particle size of the filler particles using a measuring machine (Microtrac) utilizing a laser diffraction scattering method and converting the result into a particle size distribution.
[0171] The volume average particle size of the filler particles is not particularly limited and can be appropriately selected according to the purpose, preferably 3μm to 25μm, more preferably 5μm to 20μm, and further preferably 5μm to 14μm. If the volume average particle size of the filler particles is within the preferred range, even if the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend, it can be easily stretched and peeled, even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to break, and the impact resistance, shear adhesion and split adhesion are excellent. On the other hand, if the volume average particle size of the filler particles is less than 3μm, it is sometimes difficult to stretch and peel when the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend. If it exceeds 25μm, the bonding properties such as impact resistance, shear adhesion and split adhesion are sometimes impaired.
[0172] The volume average particle size of the filler particles can be measured, for example, using a measuring device (Microtrac) utilizing a laser diffraction scattering method.
[0173] The ratio of the volume average particle size of the filler particles to the average thickness of the adhesive layer described later is not particularly limited and can be appropriately selected according to the purpose. The ratio of the volume average particle size of the filler particles to the average thickness of the adhesive layer shown in [volume average particle size of filler particles / average thickness of adhesive layer] is preferably 5 / 100 or more, more preferably 5 / 100 to 95 / 100, further preferably 10 / 100 to 75 / 100, and particularly preferably 20 / 100 to 60 / 100. If the above ratio is within the above preferred range, even if the extension direction of the adhesive sheet is 90° relative to the attachment surface of the adherend, it can be easily stretched and peeled, and even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to break. In addition, if the above ratio is within the above particularly preferred range, even if the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend, it can be easily elongated and peeled, and even if the thickness of the substrate of the adhesive sheet is thin, it is not easy to break, and it is advantageous in terms of better bonding performance such as impact resistance, shear adhesion, and split adhesion. On the other hand, if the above ratio is less than 5 / 100, the elongation and peeling performance when the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend is sometimes impaired, and if it exceeds 95 / 100, the bonding performance such as impact resistance, shear adhesion, and split adhesion is sometimes impaired.
[0174] The content of the filler particles in the adhesive layer is not particularly limited and can be appropriately selected according to the purpose. It is preferably 10 to 90 parts by weight, more preferably 15 to 50 parts by weight, and further preferably 20 to 40 parts by weight relative to 100 parts by weight of the adhesive resin. If the content of the filler particles relative to 100 parts by weight of the adhesive resin is less than 10 parts by weight, sometimes the adhesive sheet cannot be stretched and peeled off when the elongation direction of the adhesive sheet is 90° relative to the attached surface of the adherend, or sometimes the adhesive sheet breaks, and the adhesive sheet cannot be stretched and can no longer be peeled off. In addition, if the content of the filler particles relative to 100 parts by weight of the adhesive resin exceeds 90 parts by weight, the following situations exist: the adhesive sheet does not stretch, the adhesive composition remains in the adherend, the impact resistance deteriorates, and the shear bonding force and the split bonding force weaken. On the other hand, if the content of the filler particles is within the preferred range, the adhesive sheet can be easily stretched and peeled off even if the stretching direction is 90° relative to the attachment surface of the adherend, and is not easy to break even when the thickness of the substrate of the adhesive sheet is thin, and is advantageous in terms of excellent impact resistance, shear adhesion and cleavage adhesion.
[0175] The content of the filler particles in the adhesive layer may be appropriately adjusted when preparing the adhesive composition.
[0176] The volume ratio of the filler particles relative to the volume of the entire adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 4% to 40%, more preferably 5% to 30%, further preferably 5% to 20%, and particularly preferably 5% to 15%. If the volume ratio of the filler particles is less than 4%, sometimes the adhesive sheet cannot be stretched and peeled off when the elongation direction of the adhesive sheet is 90° relative to the attachment surface of the adherend, or sometimes the adhesive sheet breaks, and the adhesive sheet cannot be stretched and cannot be peeled off again. In addition, if the volume ratio of the filler particles exceeds 40%, the following situations exist: the adhesive sheet does not stretch, the adhesive composition remains on the adherend, the impact resistance deteriorates, and the shear adhesion and cleavage adhesion become weaker. On the other hand, if the volume ratio of the filler particles is within the preferred range, the adhesive sheet can be easily stretched and peeled off even if the stretching direction is 90° relative to the attachment surface of the adherend, and is not easy to break even when the thickness of the substrate of the adhesive sheet is thin, and is advantageous in terms of excellent impact resistance, shear adhesion and cleavage adhesion.
[0177] The volume ratio of the filler particles to the adhesive layer can be calculated according to the following formulas (1) to (3).
[0178] Binder resin *1Weight A(g) / Binder resin *1 Density A(g / cm 3 )=Binder resin *1 Volume A(cm 3 )···Formula (1)
[0179] Weight of filler particles B (g) / density of filler particles B (g / cm 3 ) = volume of filler particles B (cm 3 )···Formula (2)
[0180] The volume of filler particles B (cm 3 ) / (Binder resin *1 Volume A(cm 3 ) + volume of filler particles B (cm 3 ))×100=volume ratio of filler particles (%)···Formula (3)
[0181] It should be noted that in the above formulas (1) and (3), *1 The binder resin may contain other components described in the paragraph
[0079] described later.
[0182] The above density is a value measured in accordance with JIS Z 8804.
[0183] The number of the pressure-sensitive adhesive layers is not particularly limited and may be appropriately selected depending on the intended use, and the pressure-sensitive adhesive layers may be disposed on only one side or on both sides of the pressure-sensitive adhesive sheet, and are preferably disposed on both sides.
[0184] -Stress at 25% elongation of the adhesive layer-
[0185] The stress of the adhesive layer at 25% elongation is not particularly limited and can be appropriately selected according to the purpose, preferably 0.04MPa to 0.4MPa, more preferably 0.05MPa to 0.1MPa. If the stress of the adhesive layer at 25% elongation is within the preferred range, a bonding strength suitable for the adhesive sheet can be obtained, and it can be peeled off relatively easily even when the adhesive sheet is peeled off by elongation. On the other hand, if the stress of the adhesive layer at 25% elongation is less than 0.04MPa, when the load in the shear direction of the adhesive sheet is generated while fixing the hard adherends to each other, the adhesive sheet may be peeled off. If it exceeds 0.4MPa, when peeling the adhesive sheet, the force required to elongate the adhesive sheet may become too large.
[0186] The stress of the adhesive layer at an elongation of 25% refers to the stress value measured when the adhesive layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) to produce an elongation of 25%.
[0187] -Breaking point stress of adhesive layer-
[0188] As the breaking point stress of the above-mentioned adhesive layer, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably 0.5MPa~2.1MPa, and more preferably 1.0MPa~2.1MPa. If the breaking point stress of the above-mentioned adhesive layer is within the above-mentioned preferred range, when the above-mentioned adhesive sheet is stretched and peeled off, the adhesive sheet can also be suppressed from rupturing, and the load used to elongate the adhesive sheet will not be excessively excessive, so the re-peeling operation based on peeling becomes easy. On the other hand, if the breaking point stress of the above-mentioned adhesive layer is less than 0.5MPa, the adhesive sheet is sometimes broken when the above-mentioned adhesive sheet is stretched and peeled off. If it exceeds 2.1MPa, when the above-mentioned adhesive sheet is to be stretched and peeled off again, it is sometimes not possible to fully stretch and cannot be peeled off again. It should be noted that the force required to stretch the above-mentioned adhesive sheet to deform it also depends on the thickness of the adhesive sheet. For example, when the adhesive sheet with a thick thickness and a high breaking point stress is stretched and peeled off again, it is sometimes impossible to fully stretch and cannot be peeled off again.
[0189] The breaking point stress of the above-mentioned adhesive layer refers to the stress value measured when the above-mentioned adhesive layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a stretching speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and breaks.
[0190] -Elongation at breaking point of adhesive layer-
[0191] The elongation at break of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 450% to 1300%, more preferably 500% to 1200%, and further preferably 600% to 1100%. By making the elongation at break of the adhesive layer within the preferred range, both suitable adhesion and removability can be achieved.
[0192] The breaking point elongation of the above-mentioned adhesive layer refers to the tensile elongation measured when the above-mentioned adhesive layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 10 mm, and stretched in the longitudinal direction at a tensile speed of 300 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.
[0193] -Average thickness of adhesive layer-
[0194] The average thickness of the adhesive layer is not particularly limited and can be appropriately selected according to the purpose, preferably 5 μm to 150 μm, more preferably 20 μm to 120 μm, further preferably 40 μm to 110 μm, and particularly preferably 50 μm to 100 μm. The above-mentioned "average thickness of the adhesive layer" refers to the average thickness of the adhesive layer on one side of the adhesive sheet. In the case where the adhesive layer is provided on both sides of the adhesive sheet, the average thickness of the adhesive layer on one side and the average thickness of the adhesive layer on the other side may be the same thickness or different thicknesses, preferably the same thickness.
[0195] It should be noted that in the present specification, the "average thickness of the adhesive layer" refers to the average value of the thickness of a total of 25 locations obtained by cutting the above-mentioned adhesive sheet into 5 locations in the width direction at intervals of 100 mm in the length direction, and measuring the total thickness of the above-mentioned adhesive layer at 5 locations in the width direction at intervals of 100 mm in each of the above-mentioned cut surfaces using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.).
[0196] -Method for forming adhesive layer-
[0197] There is no particular limitation on the method for forming the adhesive layer, and it can be appropriately selected from known methods according to the purpose, for example, a method of forming the adhesive layer on at least one surface of the substrate layer by a hot pressing method, a casting method based on extrusion molding, a uniaxial stretching method, a sequential biaxial stretching method, a simultaneous biaxial stretching method, an inflation method, a tube method, a calendaring method, a solution method, etc. Among them, a casting method based on extrusion molding and a solution method are preferred.
[0198] Examples of the solution method include a method of directly applying a solution containing the pressure-sensitive adhesive composition onto the substrate layer using a roll coater or the like, and a method of forming the pressure-sensitive adhesive layer on a release sheet and then peeling the sheet off for use.
[0199] The release sheet is not particularly limited and can be appropriately selected according to the purpose, for example, kraft paper, glassine paper, woodfree paper, etc.; resin films such as polyethylene, polypropylene (biaxially stretched polypropylene (OPP), uniaxially stretched polypropylene (CPP)), polyethylene terephthalate (PET), etc.; laminated paper formed by laminating the above paper with a resin film, paper formed by applying a release treatment such as silicone resin to one or both sides of the paper subjected to a gap filling treatment with clay, polyvinyl alcohol, etc., etc. These can be used alone or in combination of two or more.
[0200] <<Base material layer>>
[0201] The substrate layer is not particularly limited and can be appropriately selected from known materials that can be used for pressure-sensitive adhesive sheets within a range that does not impair the properties of the pressure-sensitive adhesive sheet. It preferably contains the following substrate materials and may further contain other components as necessary.
[0202] The substrate layer may have a single-layer structure or a multi-layer structure of two, three or more layers.
[0203] -Material for base material-
[0204] As the material for the substrate, for example, styrene resins such as styrene-isoprene copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-ethylene-butylene copolymer, and styrene-ethylene-propylene copolymer can be cited; polyurethane resins such as ester polyurethane and ether polyurethane; polyolefin resins such as polyethylene and polypropylene; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polystyrene; polycarbonate; polymethylpentene; polysulfone; polyetheretherketone; polyethersulfone; polyetherimide; polyimide film; fluororesin; nylon; acrylic resin, etc. These can be used alone or in combination of two or more, preferably in combination of two or more.
[0205] Among them, the styrene resins and the polyurethane resins are preferred because they can easily provide suitable elongation at break and stress at break. The styrene resins are more preferred, and the combination of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer is particularly preferred.
[0206] --Styrene resin--
[0207] The styrene resin is a thermoplastic resin, so it has excellent formability in extrusion molding, injection molding, etc., and is easy to form the substrate layer. In addition, the styrene resin is easy to obtain particularly excellent elongation at break in the resin group generally referred to as thermoplastic resins, and can be suitably used as the substrate of the adhesive sheet.
[0208] Therefore, in the above-mentioned substrate material, the proportion of the above-mentioned styrene resin relative to the total resin components is preferably 50% to 100%, more preferably 60% to 100%, further preferably 65% to 100%, and particularly preferably 70% to 100%. By making the proportion of the above-mentioned styrene resin within the above-mentioned preferred range, a substrate layer having excellent elongation at break and stress at break can be obtained.
[0209] The above-mentioned styrene resin can be, for example, a styrene resin of a single structure of a linear structure, a branched structure or a multi-branched structure, or a mixture of styrene resins of different structures. The above-mentioned styrene resin rich in linear structure can give the above-mentioned substrate layer an excellent elongation at break. On the other hand, in the case of a branched structure or a multi-branched structure and a styrene block at the molecular end, a quasi-crosslinked structure can be adopted, which can give excellent cohesive force. Therefore, the above-mentioned styrene resin is preferably used in a mixture according to the required mechanical properties.
[0210] As the above-mentioned styrene resin, it is preferred to use a styrene resin having the structural unit represented by the above-mentioned chemical formula (1) in the range of 13% to 60% by weight relative to the total weight of the styrene resin, more preferably 15% to 50% by weight relative to the total weight of the styrene resin, further preferably 15% to 45% by weight relative to the total weight of the styrene resin, and particularly preferably 15% to 35% by weight relative to the total weight of the styrene resin. By making the ratio of the structural unit represented by the following chemical formula (1) relative to the total weight of the above-mentioned styrene resin within the above-mentioned preferred range, it is easy to obtain the elongation at break and the stress at break within the appropriate range.
[0211] When the styrene-based resin is used in combination with the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer, the content of the styrene-isoprene copolymer is preferably 0% to 80% by weight, more preferably 0% to 70% by weight, further preferably 0% to 50% by weight, and particularly preferably 0% to 30% by weight, relative to the total weight of the styrene-isoprene copolymer and the styrene-isoprene-styrene copolymer. If the content of the styrene-isoprene copolymer is within the preferred range, thermal durability can be achieved while maintaining excellent elongation at break and stress at break.
[0212] In addition, as the above-mentioned styrene-isoprene copolymer, it is preferred to use a styrene-isoprene copolymer with a weight average molecular weight of 10,000 to 800,000 measured in terms of standard polystyrene by gel permeation chromatography (GPC), more preferably a styrene-isoprene copolymer with a weight average molecular weight of 30,000 to 500,000, and even more preferably a styrene-isoprene copolymer with a weight average molecular weight of 50,000 to 300,000. By making the weight average molecular weight of the above-mentioned styrene-isoprene copolymer within the above-mentioned preferred range, it is possible to ensure heat fluidity and compatibility during solvent dilution, so that the above-mentioned substrate layer with good workability in the manufacturing process and heat durability can be obtained, which is preferred.
[0213] The measurement of the weight average molecular weight of the styrene-isoprene copolymer by the GPC method is the same as the method described in the above section "-Rubber-based Binder Resin-".
[0214] There are no particular restrictions on the method for producing the above-mentioned styrene-isoprene copolymer, the above-mentioned styrene-isoprene-styrene copolymer, and the mixture of the above-mentioned styrene-isoprene copolymer and the above-mentioned styrene-isoprene-styrene copolymer, and they can be appropriately selected from conventionally known production methods, for example, the same method as described in the above-mentioned item "-Rubber-based binder resin-" can be cited.
[0215] --Polyurethane resin--
[0216] The polyurethane resin is not particularly limited and can be appropriately selected according to the purpose. A polyurethane resin having a softening point of 40° C. or higher is preferred, and a polyurethane resin having a softening point of 50° C. or higher is more preferred. The upper limit of the softening point is preferably 100° C. or lower. The softening point is a value measured according to JIS K 2207 (dry bulb method) (hereinafter, the same applies to the softening point).
[0217] As the polyurethane resin, a reaction product of a polyol (b1-1) and a polyisocyanate (b1-2) can be preferably used.
[0218] As the above-mentioned polyol (b1-1), there is no particular limitation and it can be appropriately selected according to the purpose, for example, polyester polyol, polyether polyol, polycarbonate polyol, acrylic polyol, etc. can be cited. They can be used alone or in combination of two or more. Among them, as the above-mentioned polyol (b1-1), polyester polyol and polyether polyol can obtain the mechanical properties of the above-mentioned substrate layer, so it is preferred. In the above-mentioned substrate layer, when heat resistance is required, polyester polyol is preferably used, and when water resistance and biodegradability resistance are required, polyether polyol is preferably used.
[0219] Examples of the polyester polyol include polyesters obtained by esterification reaction of a low molecular weight polyol and a polycarboxylic acid, polyesters obtained by ring-opening polymerization of a cyclic ester compound such as ε-caprolactone, and copolymerized polyesters thereof.
[0220] Examples of the low molecular weight polyol that can be used in the production of the polyester polyol include aliphatic alkylene glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, neopentyl glycol, and 1,3-butanediol, and cyclohexanedimethanol having a weight average molecular weight of about 50 to 300.
[0221] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid; and anhydrides or esters thereof.
[0222] Examples of the polyether polyol include polyether polyols obtained by addition-polymerizing alkylene oxides using one or more compounds having two or more active hydrogen atoms as initiators.
[0223] As the polycarbonate polyol, for example, a polycarbonate polyol obtained by reacting a carbonate ester and / or phosgene with a low molecular weight polyol described below can be used.
[0224] Examples of the carbonate ester include methyl carbonate, dimethyl carbonate, ethyl carbonate, diethyl carbonate, cyclic carbonate, and diphenyl carbonate.
[0225] Examples of the low molecular weight polyol that can be used in the production of the polycarbonate polyol and can react with the carbonate and / or phosgene include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, tripropylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 1,7 ...2-butylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2,5-hexanediol, 1,7-butylene glycol, 1,2-butylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, -heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,4-cyclohexanedimethanol, hydroquinone, resorcinol, bisphenol A, bisphenol F, 4,4'-biphenol, etc.
[0226] As the above-mentioned polyisocyanate (b1-2), there is no particular limitation and it can be appropriately selected according to the purpose, for example, alicyclic polyisocyanate, aliphatic polyisocyanate, aromatic polyisocyanate etc. can be used, and alicyclic polyisocyanate etc. can be mentioned. They can be used alone or in combination of two or more.
[0227] Examples of the alicyclic polyisocyanate include isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, 2,4-methylcyclohexane diisocyanate, 2,6-methylcyclohexane diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, 2,6-norbornane diisocyanate, dimer acid diisocyanate, and bicycloheptane triisocyanate. These may be used alone or in combination of two or more.
[0228] There is no particular limitation on the method for preparing the polyurethane resin (b1) by reacting the polyol (b1-1) with the polyisocyanate (b1-2), and the method can be appropriately selected from conventionally known production methods. For example, the following method can be cited: after removing the water from the polyol (b1-1) put into a reaction container by heating under normal pressure or reduced pressure, the polyisocyanate (b1-2) is supplied all at once or in batches to react.
[0229] The reaction of the above-mentioned polyol (b1-1) and the above-mentioned polyisocyanate (b1-2) is preferably carried out in the range of 1.0 to 20.0 of the equivalent ratio (NCO / OH equivalent ratio) of the isocyanate group (NCO) possessed by the above-mentioned polyisocyanate (b1-2) to the hydroxyl group (OH) possessed by the above-mentioned polyol (b1-1), more preferably in the range of 1.1 to 13.0, further preferably in the range of 1.2 to 5.0, and particularly preferably in the range of 1.5 to 3.0.
[0230] The reaction conditions of the polyol (b1-1) and the polyisocyanate (b1-2) are not particularly limited and can be appropriately selected in consideration of various conditions such as safety, quality, and cost. The reaction temperature is preferably 70° C. to 120° C., and the reaction time is preferably 30 minutes to 5 hours.
[0231] When the polyol (b1-1) and the polyisocyanate (b1-2) are reacted, a catalyst such as a tertiary amine catalyst or an organic metal catalyst may be used as necessary.
[0232] In addition, the above reaction may be carried out in the absence of a solvent or in the presence of an organic solvent.
[0233] The organic solvent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include ester solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; ether ester solvents such as methyl cellosolve acetate and butyl cellosolve acetate; aromatic hydrocarbon solvents such as toluene and xylene; amide solvents such as dimethylformamide and dimethylacetamide, etc. These solvents can be used alone or in combination of two or more.
[0234] The organic solvent may be removed by a suitable method such as heating under reduced pressure, drying under normal pressure, etc. during the production process of the polyurethane resin (b1) or after the production of the polyurethane (b1).
[0235] --Other ingredients--
[0236] As the above-mentioned other components in the above-mentioned substrate layer, there is no particular limitation, and they can be appropriately selected within the range that does not damage the characteristics of the above-mentioned adhesive sheet, for example, tackifying resins can be cited; polymer components other than the above-mentioned substrate materials; crosslinking agents, anti-aging agents, ultraviolet absorbers, fillers, inhibitors, surface regulators, antistatic agents, defoamers, viscosity modifiers, light stabilizers, weather stabilizers, heat stabilizers, antioxidants, leveling agents, organic pigments, inorganic pigments, pigment dispersants, silica beads, organic beads and other additives; inorganic fillers such as silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, antimony pentoxide, etc. They can be used alone or in combination of two or more.
[0237] The content of the other components in the base layer may be appropriately selected within a range that does not impair the properties of the pressure-sensitive adhesive sheet.
[0238] The tackifier resin may be used for the purpose of improving the adhesion between the adhesive layer and the base layer in the adhesive sheet or improving the heat resistance.
[0239] The tackifier resin is not particularly limited and can be appropriately selected according to the purpose. A tackifier resin having a softening point of 80° C. or higher is preferred, 90° C. or higher is more preferred, 100° C. or higher is further preferred, and 110° C. or higher is particularly preferred.
[0240] As the tackifier resin, for example, the tackifier resins described in the above-mentioned item "-Rubber-based binder resin-" can be used, and the preferred embodiments and the like are also the same.
[0241] As the above-mentioned antioxidant, there is no particular limitation, and it can be appropriately selected from known antioxidants according to the purpose, for example, phenolic antioxidants, phosphorus antioxidants (sometimes also referred to as "processing stabilizers"), amine antioxidants, imidazole antioxidants, etc. can be cited. They can be used alone or in combination of two or more. Among them, the above-mentioned phenolic antioxidants and phosphorus antioxidants are preferred. When they are used in combination, the heat resistance stability of the above-mentioned substrate material can be effectively improved, and as a result, it is possible to obtain an adhesive sheet that maintains good initial adhesion and has further excellent thermal durability, so it is preferred. It should be noted that the above-mentioned phosphorus antioxidants sometimes change color (yellowing) slightly over time under high temperature conditions, and therefore, its usage is preferably appropriately set in consideration of the above-mentioned initial adhesion, thermal durability and the balance of preventing discoloration.
[0242] As the above-mentioned phenolic antioxidant, phenolic compounds having sterically hindered groups can generally be used, and representative ones are monophenol type, bisphenol type, and polyphenol type. As specific examples, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(6-tert-butyl-3-methylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), tetrakis[methylene-3-(3'5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane, 3-(4'-hydroxy-3'5'-di-tert-butylphenyl)propionic acid n-octadecyl ester, etc. can be cited. They can be used alone or in combination of two or more.
[0243] The amount of the phenolic antioxidant used is not particularly limited and can be appropriately selected according to the purpose. It is preferably used in the range of 0.1 to 5 parts by weight relative to 100 parts by weight of the substrate material. When used in the range of 0.5 to 3 parts by weight, the heat resistance stability of the substrate material can be effectively improved. As a result, an adhesive sheet that maintains good initial adhesion and has further excellent thermal durability can be obtained.
[0244] -Stress at 25% elongation of the substrate layer-
[0245] The stress of the substrate layer at 25% elongation is not particularly limited and can be appropriately selected according to the purpose, preferably 0.2MPa to 10.0MPa, more preferably 0.2MPa to 5.0MPa, further preferably 0.2MPa to 3.0MPa, and particularly preferably 0.2MPa to 2.0MPa. If the stress of the substrate layer at 25% elongation is within the preferred range, a bonding strength suitable for the adhesive sheet can be obtained, and it can be peeled off relatively easily even when the adhesive sheet is peeled off by elongation. On the other hand, if the stress of the substrate layer at 25% elongation is less than 0.2MPa, when the load in the shear direction of the adhesive sheet is generated while the hard adherends are fixed to each other, the adhesive sheet is sometimes peeled off. If it exceeds 10.0MPa, when the adhesive sheet is peeled off, the force required to stretch the adhesive sheet sometimes becomes too large.
[0246] The stress at which the substrate layer is elongated by 25% refers to the stress value measured when the substrate layer is punched into a dumbbell shape with a marking length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min under the conditions of a measuring atmosphere of 23°C and 50% RH using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.).
[0247] - Breaking point stress of substrate layer-
[0248] As the breaking point stress of the above-mentioned substrate layer, there is no particular limitation and it can be appropriately selected according to the purpose, preferably 1.5MPa~100.0MPa, more preferably 7.0MPa~50.0MPa, further preferably 7.0MPa~40.0MPa, and particularly preferably 8.0MPa~35.0MPa. If the breaking point stress of the above-mentioned substrate layer is within the above-mentioned preferred range, when the above-mentioned adhesive sheet is stretched and peeled off, the adhesive sheet can also be suppressed from rupturing, and the load used to stretch the adhesive sheet will not be excessively excessive, so the re-peeling operation based on peeling becomes easy. On the other hand, if the breaking point stress of the above-mentioned substrate layer is less than 1.5MPa, when the above-mentioned adhesive sheet is stretched and peeled off, the adhesive sheet sometimes ruptures. If it exceeds 100.0MPa, when the above-mentioned adhesive sheet is stretched and peeled off, it is sometimes not possible to fully stretch and cannot be peeled off. It should be noted that the force required to stretch and deform the above-mentioned adhesive sheet also depends on the thickness of the adhesive sheet. For example, when one wants to stretch and peel off a thick adhesive sheet with high breaking point stress, it may not be stretched sufficiently and cannot be peeled off.
[0249] The breaking point stress of the above-mentioned substrate layer refers to the stress value measured when the above-mentioned substrate layer is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and when the layer breaks.
[0250] -Elongation at break of substrate layer-
[0251] The elongation at break of the substrate layer is not particularly limited and can be appropriately selected according to the purpose, preferably 200% to 1300%, more preferably 400% to 1300%, and further preferably 700% to 1300%. If the elongation at break of the substrate layer is 200% or more, even if the adhesive sheet is firmly bonded to the adherend, when the adhesive sheet is peeled off again, the stress for stretching in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too large, and the adhesive sheet will not be over-stretched during peeling, and can be easily peeled off. In addition, if the elongation at break is 1300% or less, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too long, and the operation can be performed in a small space. On the other hand, if the elongation at breaking point is less than 200%, when the adhesive sheet is peeled off again, it may be impossible to peel off due to breakage when it is stretched and peeled off in the horizontal direction to the vertical direction relative to the attached surface of the adherend. If it exceeds 1300%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attached surface of the adherend becomes too long, so the workability may be deteriorated.
[0252] The elongation at break of the substrate layer refers to the tensile elongation measured when the substrate layer is punched into a dumbbell shape with a marking length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.
[0253] -Average thickness of substrate layer-
[0254] The average thickness of the substrate layer is not particularly limited and can be appropriately selected according to the purpose of use, and is preferably 10 μm to 500 μm, more preferably 10 μm to 300 μm, further preferably 20 μm to 200 μm, and particularly preferably 20 μm to 100 μm. If the average thickness of the substrate layer is within the preferred range, the adhesive sheet can easily follow the strain of the adherend, and high bonding strength can be easily obtained. The stress required for re-peeling the adhesive sheet having the substrate layer while stretching it in the horizontal direction to the vertical direction relative to the attachment surface of the adherend will not become too large, so it is preferred.
[0255] It should be noted that, in this specification, the "average thickness of the substrate layer" means that the above-mentioned substrate layer is cut into 5 places at intervals of 100 mm in the length direction along a direction perpendicular to the length direction (sometimes also referred to as the "width direction"), and in each of the above-mentioned cut surfaces, the thickness is measured at 5 places at intervals of 100 mm in the width direction using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.), to obtain an average value of the thickness at a total of 25 places.
[0256] -Average thickness of adhesive layer / Average thickness of substrate layer-
[0257] As the ratio of the thickness of the above-mentioned adhesive layer to the above-mentioned substrate layer, there is no particular restriction and it can be appropriately selected according to the purpose. The ratio of the average thickness of the above-mentioned adhesive layer relative to the average thickness of the above-mentioned substrate layer, represented by [average thickness of the adhesive layer / average thickness of the substrate layer], is preferably 1 / 5 to 5 / 1, more preferably 1 / 3 to 3 / 1, and further preferably 1 / 1 to 2 / 1. If the ratio of the average thickness of the above-mentioned adhesive layer to the average thickness of the above-mentioned substrate layer is within the above-mentioned preferred range, the excellent adhesion and re-peelability of the above-mentioned adhesive sheet can be obtained. On the other hand, if the above-mentioned ratio is greater than 5 / 1, it is possible that only the above-mentioned adhesive layer remains on the adherend in the re-peeling process of the above-mentioned adhesive sheet. In addition, if the above-mentioned ratio is less than 1 / 5, when the surface of the adherend is a concave-convex shape, etc., it is possible that the adhesive layer cannot follow and the bonding strength is significantly reduced.
[0258] -Method for forming base material layer-
[0259] There is no particular limitation on the method for forming the substrate layer. It can be appropriately selected from known methods according to the mechanical strength required for the adhesive sheet, such as hot pressing, casting based on extrusion molding, uniaxial stretching, sequential biaxial stretching, simultaneous biaxial stretching, inflation, tube method, calendering, solution method, etc. These methods can be used alone or in combination of two or more. Among them, casting based on extrusion molding, inflation, tube method, calendering, solution method are preferred in terms of imparting appropriate softness and stretchability to the substrate layer.
[0260] In addition, the base layer may be subjected to a surface treatment for the purpose of further improving the adhesion with the adhesive layer.
[0261] The surface treatment method is not particularly limited and can be appropriately selected from known methods within the range that does not impair the properties of the adhesive sheet. Examples thereof include sandblasting, surface grinding and friction, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet irradiation treatment, oxidation treatment, and the like.
[0262] <<Other layers>>
[0263] The other layers in the pressure-sensitive adhesive sheet are not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include a primer layer, an antistatic layer, a non-combustible layer, a decorative layer, a conductive layer, a thermal conductive layer, and a release layer.
[0264] -Stress of adhesive sheet at 25% elongation-
[0265] As the stress at 25% elongation of the above-mentioned adhesive sheet, there is no particular limitation and it can be appropriately selected according to the purpose, preferably 0.15Mpa to 82Mpa, more preferably 0.15Mpa to 10Mpa, further preferably 0.15Mpa to 5Mpa, and particularly preferably 0.15Mpa to 2Mpa. If the stress at 25% elongation of the above-mentioned adhesive sheet is 0.15Mpa to 82Mpa, it is possible to obtain an adhesive strength suitable for the above-mentioned adhesive sheet, and it can be peeled off relatively easily even when the elongation is peeled off. On the other hand, if the stress at 25% elongation of the above-mentioned adhesive sheet is less than 0.15Mpa, when the load in the shear direction of the above-mentioned adhesive sheet is generated while the hard adherends are fixed to each other, the above-mentioned adhesive sheet is sometimes peeled off. In addition, if the stress at 25% elongation of the above-mentioned adhesive sheet exceeds 82Mpa, when the above-mentioned adhesive sheet is peeled off, the force required to elongate the adhesive sheet sometimes becomes too large.
[0266] The stress at 25% elongation of the above-mentioned adhesive sheet refers to the stress value measured when the above-mentioned adhesive sheet is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and when an elongation of 25% occurs.
[0267] -Breaking point stress of adhesive sheet-
[0268] As the breaking point stress of the above-mentioned adhesive sheet, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably 1.5MPa~100.0MPa, more preferably 5.0MPa~50.0MPa, further preferably 5.0MPa~40.0MPa, and particularly preferably 5.0MPa~35.0MPa. If the breaking point stress of the above-mentioned adhesive sheet is within the above-mentioned preferred range, the adhesive sheet can also be suppressed from rupturing when the above-mentioned adhesive sheet is stretched and peeled off, and the load used to stretch the adhesive sheet will not be excessively excessive, so the re-peeling operation based on peeling becomes easy. On the other hand, if the breaking point stress of the above-mentioned adhesive sheet is less than 1.5MPa, when the above-mentioned adhesive sheet is stretched and peeled off, the adhesive sheet sometimes breaks, and if it exceeds 100.0MPa, when the above-mentioned adhesive sheet is stretched and peeled off again, it is sometimes not possible to fully stretch and cannot be peeled off again. It should be noted that the force required to stretch and deform the above-mentioned adhesive sheet also depends on the thickness of the adhesive sheet. For example, when one wants to stretch and peel off a thick adhesive sheet with high breaking point stress, it may not be stretched sufficiently and cannot be peeled off.
[0269] The breaking point stress of the above-mentioned adhesive sheet refers to the stress value measured when the above-mentioned adhesive sheet is punched into a dumbbell shape with a marking line length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a stretching speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, and breaks.
[0270] -Elongation at Break of Adhesive Sheet-
[0271] The elongation at break of the adhesive sheet is not particularly limited and can be appropriately selected according to the purpose, preferably 500% to 2000%, more preferably 600% to 1800%, and further preferably 800% to 1800%. If the elongation at break of the adhesive sheet is 500% or more, even if the adhesive sheet is firmly bonded to the adherend, when the adhesive sheet is peeled off again, the stress for stretching in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too large, and the adhesive sheet can be easily peeled off without excessive elongation during peeling. In addition, if the elongation at break is less than 2000%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attached surface of the adherend will not become too long, and the operation can be performed in a small space. On the other hand, if the elongation at breaking point is less than 500%, when the adhesive sheet is peeled off again, it may be impossible to peel off due to breakage when it is stretched in the horizontal direction to the vertical direction relative to the attachment surface of the adherend. If it exceeds 1300%, when the adhesive sheet is peeled off again, the stretching distance in the horizontal direction to the vertical direction relative to the attachment surface of the adherend will not become too long, so the workability may be deteriorated.
[0272] The elongation at break of the adhesive sheet is the tensile elongation measured when the adhesive sheet is punched into a dumbbell shape with a marking length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH.
[0273] -Impact resistance of adhesive sheet-
[0274] The above-mentioned adhesive sheet has excellent impact resistance. The above-mentioned impact resistance can be confirmed, for example, by the method described in <<Evaluation of impact resistance>> in the examples described later. In the above-mentioned impact resistance evaluation, the height of the impact core that causes peeling or destruction of the adhesive sheet can be appropriately selected within the range that does not impair the effect of the present invention, preferably 30 cm or more, more preferably 40 cm or more, further preferably 50 cm or more, and particularly preferably 60 cm or more. If the above-mentioned height is less than 30 cm, sufficient impact resistance cannot be obtained.
[0275] -180° Peel Adhesion of PSA Sheet-
[0276] The 180° peeling strength of the adhesive sheet is not particularly limited and can be appropriately selected according to the purpose, preferably 3N / 20mm to 35N / 20mm, more preferably 4N / 20mm to 30N / 20mm, and further preferably 5N / 20mm to 25N / 20mm. If the 180° peeling strength is within the preferred range, the adhesive sheet has a moderate adhesive strength without causing peeling or displacement from the adherend, and can be easily peeled off when the adhesive sheet is stretched in the horizontal direction to the vertical direction relative to the attachment surface of the adherend and then peeled off.
[0277] The 180° peel strength of the pressure-sensitive adhesive sheet is a value measured in accordance with JIS Z 0237.
[0278] -Shear Adhesion Strength of Adhesive Sheets-
[0279] The adhesive sheet is not easily peeled off even when a load is applied in the shear direction of the adhesive sheet, and has excellent shear adhesion. It should be noted that the shear direction is not particularly limited as long as it is a direction perpendicular to the thickness direction of the adhesive sheet.
[0280] The shear adhesive strength of the pressure-sensitive adhesive sheet can be appropriately selected within a range that does not impair the effects of the present invention, and is preferably 100 N / 4 cm 2 More than, more preferably 120N / 4cm 2 More than, more preferably 150N / 4cm 2 Above, particularly preferably 200N / 4cm 2 When the shear adhesive strength is within the preferred range, it is possible to suppress displacement when stress in the shear direction is applied to an adherend fixed by the pressure-sensitive adhesive sheet.
[0281] The shear adhesive strength of the pressure-sensitive adhesive sheet can be confirmed, for example, by the method described in "Measurement of Shear Adhesive Strength" in the Examples described later.
[0282] -Separation and Adhesion Strength of Adhesive Sheet-
[0283] The adhesive sheet is not easily peeled off even when a load is applied in the splitting direction (sometimes also referred to as the "thickness direction") of the adhesive sheet, and has excellent splitting adhesion. The splitting adhesion of the adhesive sheet can be appropriately selected within a range that does not impair the effect of the present invention, and is preferably 80 N / 4 cm 2 More than, more preferably 100N / 4cm 2 More than, more preferably 120N / 4cm 2 When the cleavage adhesive strength is within the preferred range, it is possible to suppress peeling when stress in the cleavage direction is applied to an adherend fixed by the pressure-sensitive adhesive sheet.
[0284] The split adhesive strength of the pressure-sensitive adhesive sheet can be confirmed, for example, by the method described in "Measurement of split adhesive strength" in Examples described later.
[0285] -Average thickness of adhesive sheet-
[0286] The average thickness of the adhesive sheet is not particularly limited and can be appropriately selected based on the average thickness of the adhesive layer and the substrate layer. It is preferably 15 μm to 800 μm, more preferably 30 μm to 540 μm, further preferably 60 μm to 320 μm, and particularly preferably 70 μm to 250 μm.
[0287] It should be noted that, in the present specification, the “average thickness of the adhesive layer” means that the above-mentioned adhesive sheet is cut into 5 places in the width direction at intervals of 100 mm in the length direction, and in each of the above-mentioned cut surfaces, the thickness of the above-mentioned adhesive layer is measured at 5 places in the width direction at intervals of 100 mm using a TH-104 paper / film thickness measuring machine (manufactured by TESTER SANGYO Co., Ltd.), to obtain the average value of the thickness at a total of 25 places.
[0288] -Average width of adhesive sheet-
[0289] The average width of the adhesive sheet is not particularly limited and can be appropriately selected according to the type of electronic component. The electronic components to be attached are displays, speakers, batteries, etc. The average width of the adhesive sheet when fixing them can be appropriately adjusted according to the effectiveness of the display screen and the attachment space, preferably 1 mm to 50 mm, more preferably 1 mm to 25 mm, and further preferably 0.5 mm to 10 mm.
[0290] In this specification, the “average width of the PSA sheet” refers to the average value of the total width of five locations measured at intervals of 100 mm in the longitudinal direction of the PSA sheet using a known gauge such as a scale, a tape measure, or a crown.
[0291] <<Method for producing adhesive sheet>>
[0292] There is no particular limitation on the method for manufacturing the adhesive sheet, and it can be appropriately selected from known methods, preferably including an adhesive layer forming step, a substrate layer forming step and a lamination step, and further including other layer forming steps as required. In addition, it can also be manufactured by a multi-layer simultaneous forming step of simultaneously performing the adhesive layer forming step and the substrate layer forming step.
[0293] -Adhesive layer forming step-
[0294] The adhesive layer forming step is not particularly limited as long as the adhesive layer can be formed, and may be appropriately selected depending on the purpose. For example, the same method as described in the above “adhesive layer forming method” may be mentioned, and preferred aspects are also the same.
[0295] -Base material layer forming step-
[0296] The base layer forming step is not particularly limited as long as the base layer can be formed, and may be appropriately selected according to the purpose. For example, the same method as described in the above “base layer forming method” may be mentioned, and preferred aspects are also the same.
[0297] -Lamination process-
[0298] The lamination step is a step of laminating the substrate layer and the adhesive layer. There is no particular limitation on the method of laminating the substrate layer and the adhesive layer, and the method can be appropriately selected from known methods, such as a method of laminating the substrate layer and the adhesive layer by pressurizing the substrate layer and the adhesive layer.
[0299] <Method for manufacturing electronic components>
[0300] The method for producing the electronic component is not particularly limited and may be appropriately selected depending on the intended purpose. The method preferably includes an attaching step and a fixing step, and further includes other steps as necessary.
[0301] <<Attachment process>>
[0302] The attaching step is a step of attaching the pressure-sensitive adhesive sheet to the first attachment target such that at least a portion of the surface of the pressure-sensitive adhesive sheet is in a linear shape.
[0303] The pressure-sensitive adhesive sheet, the first attachment target, and the embodiment of attaching the pressure-sensitive adhesive sheet so that at least a portion of the pressure-sensitive adhesive sheet is in a linear shape are as described above.
[0304] <<Fixing process>>
[0305] The fixing step is a step of attaching the other surface of the adhesive sheet to the second attachment target with at least two end portions of the adhesive sheet exposed from the second attachment target.
[0306] The state in which the second attachment object and at least two end portions are exposed from the second attachment object is as described above.
[0307] The electronic component is provided with an adhesive sheet, which can be quickly peeled off without contamination caused by the adhesive after peeling off. Even if the adhesive sheet is broken in the middle of being stretched and peeled off from one end, it can be stretched and peeled off from the other end to the end, and has appropriate adhesive force when used. Therefore, it can be used as a wide range of electronic components, regardless of the size of the electronic components, such as large electronic devices such as thin-film televisions, home appliances, and OA equipment, and components constituting the same, and small electronic devices such as portable electronic terminals, cameras, and personal computers, and components constituting the same.
[0308] Example
[0309] Hereinafter, the present invention will be specifically described with reference to test examples etc., but the present invention is not limited to these examples at all.
[0310] In the production of the adhesive sheets (1) to (11) of the following Production Examples 1 to 11, the following compositions were used as the resin compositions (1) to (3) in the base layer and the adhesive compositions (1) to (8) in the adhesive layer.
[0311] <Resin composition (1)>
[0312] As the above-mentioned resin composition (1), a mixture of a styrene-isoprene copolymer and a styrene-isoprene-styrene copolymer (hereinafter sometimes referred to as "SIS") is used, wherein the structural unit derived from styrene represented by the following chemical formula (1) accounts for 25% by weight, and the ratio of the styrene-isoprene copolymer to the total amount of the above-mentioned resin composition (1) is 17% by weight.
[0313] [Chemical formula 2]
[0314]
[0315] <Resin composition (2)>
[0316] As the resin composition (2), an ester polyurethane compound (Mobilon Film MF 100T, manufactured by Nisshinbo Textile Co., Ltd.) was used.
[0317] <Resin composition (3)>
[0318] As the resin composition (3), a mixture of styrene-isoprene copolymer and styrene-isoprene-styrene copolymer (SIS) is used, wherein the structural unit derived from styrene represented by the chemical formula (1) is 15% by weight, and the proportion of the styrene-isoprene copolymer relative to the total amount of the resin composition (3) is 12% by weight.
[0319] (Preparation Example 1: Preparation of Adhesive Composition (1))
[0320] In a reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer and a dropping funnel, 75.94 parts by weight of n-butyl acrylate, 5 parts by weight of 2-ethylhexyl acrylate, 15 parts by weight of cyclohexyl acrylate, 4 parts by weight of acrylic acid, 0.06 parts by weight of 4-hydroxybutyl acrylate and 200 parts by weight of ethyl acetate were added, and the mixture was heated to 65° C. while nitrogen was blown in under stirring to obtain a mixture (1). Next, 4 parts by weight of a 2,2'-azobisisobutyronitrile solution (solid content 2.5% by weight) dissolved in ethyl acetate in advance was added to the mixture (1), and the mixture was kept at 65° C. for 10 hours under stirring to obtain a mixture (2). Next, the mixture (2) was diluted with 98 parts by weight of ethyl acetate and filtered through a 200-mesh metal screen to obtain an acrylic copolymer solution (1) having a weight average molecular weight of 1.6 million (polystyrene conversion). Next, 5 parts by weight of a polymerized rosin ester tackifier resin (D-125, Arakawa Chemical Industries, Ltd.) and 15 parts by weight of a petroleum tackifier resin (FTR (registered trademark) 6125, manufactured by Mitsui Chemicals, Inc.) were added to 100 parts by weight of the acrylic copolymer solution (1), and the mixture was stirred and mixed, and then ethyl acetate was added to obtain a binder resin solution (1) having a solid content of 31% by weight. Next, 1 part by weight of carbon black (MA220, manufactured by Mitsubishi Chemical Corporation) and 1.3 parts by weight of a crosslinking agent (Burnock D-40, manufactured by DIC Corporation; trimethylolpropane adduct of toluene diisocyanate, isocyanate group content of 7% by weight, non-volatile matter of 40% by weight) were added to 100 parts by weight of the binder resin solution (1), and the mixture was stirred and mixed until uniform, and then filtered through a 100-mesh metal mesh to obtain a binder resin (1) having a solid content of 31.1% by weight.
[0321] (Preparation Example 2: Preparation of Adhesive Composition (2))
[0322] Filler 1 (aluminum hydroxide, BW153, manufactured by Nippon Light Metal Co., Ltd., volume average particle size: 18 μm, particle size distribution (D 90 / D 10 ): 12.3) 30 parts by weight to obtain an adhesive composition (2).
[0323] It should be noted that the particle size distribution (D 90 / D 10 ) is a value obtained by measuring the particle size of the filler particles using a measuring machine (Microtrac) utilizing a laser diffraction scattering method and converting the result into a particle size distribution.
[0324] (Preparation Example 3: Preparation of Adhesive Composition (3))
[0325] In the above Preparation Example 2, except that the type and addition amount of the filler were changed to the type and addition amount shown in the following Table 1, an adhesive composition (3) was prepared by the same method as in the above Preparation Example 2.
[0326] Note that filler 2 is nickel powder (Type 123, manufactured by Inco Corporation, volume average particle size: 11.9 μm), and the particle size distribution (D 90 / D 10 ) is 4.2.
[0327] (Preparation Example 4: Preparation of Adhesive Composition (4))
[0328] In the above-mentioned Preparation Example 2, except having changed the kind of filler into the kind shown in the following Table 2, it carried out similarly to the method of the above-mentioned Preparation Example 2, and prepared the adhesive composition (4).
[0329] It should be noted that filler 3 is aluminum hydroxide (B303, manufactured by Nippon Light Metal Co., Ltd., volume average particle size: 23 μm), and the particle size distribution (D 90 / D 10 ) is 18.5.
[0330] (Preparation Example 5: Preparation of Adhesive Composition (5))
[0331] In the above-mentioned Preparation Example 2, except having changed the kind of filler into the kind shown in the following Table 2, it carried out similarly to the method of the above-mentioned Preparation Example 2, and prepared the adhesive composition (5).
[0332] It should be noted that filler 4 is aluminum hydroxide (BE033, manufactured by Nippon Light Metal Co., Ltd., volume average particle size: 3 μm), and the particle size distribution (D 90 / D 10 ) is 5.8.
[0333] (Preparation Example 6: Preparation of Adhesive Composition (6))
[0334] In the above-mentioned Preparation Example 2, except having changed the addition amount of the filler into the addition amount shown in the following Table 2, it carried out similarly to the method of the above-mentioned Preparation Example 2, and prepared the adhesive composition (6).
[0335] (Preparation Example 7: Preparation of Adhesive Composition (7))
[0336] In the above-mentioned Preparation Example 2, except having changed the addition amount of the filler into the addition amount shown in the following Table 2, it carried out similarly to the method of the above-mentioned Preparation Example 2, and prepared the adhesive composition (7).
[0337] (Preparation Example 8: Preparation of Adhesive Composition (8))
[0338] In a reaction container equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer and a dropping funnel, 97.97 parts by weight of n-butyl acrylate, 2.0 parts by weight of acrylic acid, 0.03 parts by weight of 4-hydroxybutyl acrylate and 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator were dissolved in a solvent consisting of 100 parts by weight of ethyl acetate, and polymerization was carried out at 70°C for 12 hours to obtain an acrylic copolymer solution (2) having a weight average molecular weight of 2,000,000 (in terms of polystyrene). Next, 25 parts by weight of a glycerol ester of disproportionated rosin (SUPERESTERA100, manufactured by Arakawa Chemical Industries, Ltd.), 5 parts by weight of a pentaerythritol ester of polymerized rosin (PENSEL D135, manufactured by Arakawa Chemical Industries, Ltd.), and 20 parts by weight of a styrene-based petroleum resin (FTR (registered trademark) 6100, manufactured by Mitsui Chemicals, Inc.) were added to 100 parts by weight of the acrylic copolymer solution (2), and ethyl acetate was added and uniformly mixed to obtain a binder solution (2) having a solid content of 31% by weight. Next, 1.3 parts by weight of an isocyanate crosslinking agent (Coronate L-45, manufactured by Nippon Polyurethane Industry Co., Ltd., non-volatile content of 45% by weight) was added to 100 parts by weight of the binder solution (2), and the mixture was stirred and mixed until uniform, thereby obtaining a binder resin (2) having a solid content of 31.1% by weight.
[0339] Next, filler 1 (aluminum hydroxide, BW153, manufactured by Nippon Light Metal Co., Ltd., volume average particle size: 18 μm, particle size distribution (D 90 / D 10 ): 12.3) 30 parts by weight to obtain an adhesive composition (8).
[0340] (Manufacturing Example 1: Manufacture of Pressure-sensitive Adhesive Sheet (1))
[0341] The adhesive composition (1) was applied onto a release liner (Film Vina 75E-0010GT, manufactured by Fujimori Industries, Ltd., hereinafter the same) using an applicator to a thickness of 25 μm after drying, and dried at 80° C. for 3 minutes to prepare an adhesive layer.
[0342] Next, toluene was added to the resin composition (1), and the mixture was stirred to be uniform. The mixture was applied onto a release liner using an applicator to a thickness of 100 μm after drying, and dried at 60° C. for 5 minutes to prepare a base layer.
[0343] After the release liner of the substrate layer was peeled off, the adhesive layer from which the release liner was peeled off was bonded to both surfaces of the substrate layer, and the laminated structure of the substrate layer and the adhesive layer was pressed at 0.2 MPa to produce an adhesive sheet (1).
[0344] (Manufacturing Example 2: Manufacture of Pressure-sensitive Adhesive Sheet (2))
[0345] In the production of the adhesive sheet (1) of Production Example 1, an adhesive sheet (2) was produced in the same manner as in Production Example 1 except that the thickness of the substrate layer, the type of the adhesive composition, and the thickness of the adhesive layer were changed to the conditions described in Table 1.
[0346] (Manufacturing Example 3: Manufacture of Pressure-sensitive Adhesive Sheet (3))
[0347] In the production of the pressure-sensitive adhesive sheet (1) of Production Example 1, a pressure-sensitive adhesive sheet (3) was produced by the same method as in Production Example 1 except that the type of the pressure-sensitive adhesive composition was changed to the conditions described in Table 1.
[0348] (Manufacturing Example 4: Manufacture of Pressure-sensitive Adhesive Sheet (4))
[0349] In the production of the pressure-sensitive adhesive sheet (1) of Production Example 1, a pressure-sensitive adhesive sheet (4) was produced by the same method as in Production Example 1 except that the type of the pressure-sensitive adhesive composition was changed to the conditions described in Table 1.
[0350] (Manufacturing Example 5: Manufacture of Adhesive Sheet (5))
[0351] In the production of the adhesive sheet (1) of Production Example 1, an adhesive sheet (5) was produced in the same manner as in Production Example 1 except that the types of the resin composition in the substrate layer and the adhesive composition were changed to the conditions described in Table 1.
[0352] (Manufacturing Example 6: Manufacture of Pressure-sensitive Adhesive Sheet (6))
[0353] In the production of the adhesive sheet (1) of Production Example 1, an adhesive sheet (6) was produced by the same method as in Production Example 1, except that the type of the resin composition in the substrate layer, the thickness of the substrate layer, the type of the adhesive composition, and the thickness of the adhesive layer were changed to the conditions described in Table 1.
[0354] (Manufacturing Example 7: Manufacture of Adhesive Sheet (7))
[0355] In the production of the pressure-sensitive adhesive sheet (1) of Production Example 1, a pressure-sensitive adhesive sheet (7) was produced by the same method as in Production Example 1 except that the type of the pressure-sensitive adhesive composition was changed to the conditions described in Table 2.
[0356] (Manufacturing Example 8: Manufacture of Adhesive Sheet (8))
[0357] In the production of the PSA sheet (1) of Production Example 1, a PSA sheet (8) was produced in the same manner as in Production Example 1 except that the thickness of the substrate layer, the type of the PSA composition, and the thickness of the PSA layer were changed to the conditions described in Table 2.
[0358] (Manufacturing Example 9: Manufacture of Pressure-sensitive Adhesive Sheet (9))
[0359] In the production of the pressure-sensitive adhesive sheet (1) of Production Example 1, a pressure-sensitive adhesive sheet (9) was produced in the same manner as in Production Example 1 except that the thickness of the substrate layer and the type of the pressure-sensitive adhesive composition were changed to the conditions described in Table 2.
[0360] (Manufacturing Example 10: Manufacture of Pressure-sensitive Adhesive Sheet (10))
[0361] In the production of the pressure-sensitive adhesive sheet (1) of Production Example 1, a pressure-sensitive adhesive sheet (10) was produced in the same manner as in Production Example 1 except that the thickness of the substrate layer and the type of the pressure-sensitive adhesive composition were changed to the conditions described in Table 2.
[0362] (Manufacturing Example 11: Manufacture of Pressure-sensitive Adhesive Sheet (11))
[0363] In the production of the pressure-sensitive adhesive sheet (1) of Production Example 1, a pressure-sensitive adhesive sheet (11) was produced in the same manner as in Production Example 1 except that the thickness of the substrate layer and the type of the pressure-sensitive adhesive composition were changed to the conditions described in Table 2.
[0364] The stress, breaking stress and breaking elongation of the substrate layer in the adhesive sheets (1) to (11) of manufacturing examples 1 to 11 at an elongation of 25%; the stress, breaking stress, breaking elongation and filler volume ratio of the adhesive layer in the adhesive sheets (1) to (11) of manufacturing examples 1 to 11; and the stress, breaking stress, breaking elongation, impact resistance, 180° peeling adhesion, shear adhesion and cleavage adhesion of the adhesive sheets (1) to (11) of manufacturing examples 1 to 11 at an elongation of 25% were measured or evaluated by the following methods. The results are shown in the following Tables 1 and 2.
[0365] <<Measurement of stress at 25% elongation, stress at break, and elongation at break of pressure-sensitive adhesive sheet or substrate layer>>
[0366] Each adhesive sheet or each substrate layer was punched into a dumbbell shape with a marking length of 20 mm and a width of 6 mm, and stretched in the longitudinal direction at a tensile speed of 500 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) under the conditions of a measuring atmosphere of 23°C and 50% RH, thereby measuring the stress, breaking point stress and breaking point elongation of each adhesive sheet or each substrate layer when elongated by 25%.
[0367] <<Measurement of stress at 25% elongation, stress at break, and elongation at break of adhesive layer>>
[0368] Each adhesive layer was punched into a dumbbell shape with a marking line length of 20 mm and a width of 10 mm. Under the conditions of a measuring atmosphere of 23°C and 50% RH, the adhesive layer was stretched in the longitudinal direction at a tensile speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.), and the stress, breaking point stress and breaking point elongation of each adhesive layer at an elongation of 25% were measured.
[0369] <<Measurement of volume ratio of filler particles in adhesive layer>>
[0370] The volume ratio of the filler in each adhesive layer was calculated according to the following formulas (1) to (3).
[0371] Weight of binder resin A (g) / density of binder resin A (g / cm 3 ) = Volume of binder resin A (cm 3 )···Formula (1)
[0372] Weight of filler particles B (g) / density of filler particles B (g / cm 3 ) = volume of filler particles B (cm 3 )···Formula (2)
[0373] The volume of filler particles B (cm 3 ) / (volume of binder resin A(cm 3 ) + volume of filler particles B (cm 3 ))×100=volume ratio of filler particles (%)···Formula (3)
[0374] It should be noted that the density A of the binder resin was set to 1.2 g / cm 3 As the density B of the filler particles, the density of aluminum hydroxide is set to 2.42 g / cm 3 , the density of nickel is set to 8.90 g / cm 3 And calculate.
[0375] <<Evaluation of impact resistance>>
[0376] Each adhesive sheet was cut into pieces with a length of 20 mm and a width of 5 mm, and two pieces were prepared. Figure 5A As shown in FIG. 1 , the adhesive sheet 31 is attached in parallel to an acrylic plate 32 (length 50 mm, width 50 mm, thickness 2 mm, Acrylite L, color tone: colorless, manufactured by MITSUBISHI RAYON Co., Ltd.) at intervals of 40 mm. Figure 5B As shown, an acrylic plate 32 attached with the above-mentioned adhesive sheet 31 is attached to the central part of an ABS plate 33 (length 150 mm, width 100 mm, thickness 2 mm, TAFACE R, manufactured by Sumitomo Bakelite Co., Ltd., color: natural, no wrinkles), and a load of 2 kg is applied to the laminated structure of the above-mentioned acrylic plate 32, the above-mentioned adhesive sheet 31, and the above-mentioned ABS plate 33. After being pressed together by reciprocating pressure with a roller once, it is left to stand for 24 hours under the conditions of an atmosphere of 40°C and 50% RH to be used as a test piece.
[0377] like Figure 5C As shown, a U-shaped measuring table 34 (aluminum with a length of 150 mm, a width of 100 mm, a height of 45 mm, and a thickness of 5 mm) is set on the base of a DuPont impact tester (manufactured by TESTER SANGYO Co., Ltd.), and the above-mentioned test piece is placed on it in a manner that the acrylic plate 32 in the test piece faces downward. Under the conditions of an atmosphere of 23°C and 50% RH, a stainless steel impact core (diameter 25 mm, weight 300 g) 35 is dropped from the side of the ABS plate 33 to the center of the ABS plate 33. At this time, while changing the height of the impact core 35 by 10 cm at a time from 10 cm, the impact core 35 is dropped 5 times at intervals of 10 seconds at each height, and the height at which the peeling or destruction of the adhesive sheet in the above-mentioned test piece is confirmed is measured. It should be noted that the case where there is no peeling or destruction of the adhesive sheet when falling from more than 30 cm is a case where there is no problem in use.
[0378] <<Measurement of 180° Peel Adhesion Strength>>
[0379] The 180° peeling adhesion of each adhesive sheet was measured in accordance with JIS Z 0237. Specifically, each adhesive sheet was cut into pieces of 150 mm in length and 20 mm in width, and one side of the adhesive sheet was backed with a PET film of 25 μm in thickness. Next, the other side of the adhesive sheet was attached to a stainless steel plate (length 100 mm, width 30 mm, thickness 3 mm) under the conditions of an atmosphere of 23° C. and 50% RH, and a load of 2 kg was applied to the laminated structure of the adhesive sheet and the stainless steel plate, and the laminated structure was pressed once by a roller reciprocatingly, and then left to stand for 1 hour under the conditions of an atmosphere of 23° C. and 50% RH to serve as a test piece.
[0380] The PSA sheet in the test piece was stretched in a 180° direction (horizontal direction) at a tension rate of 300 mm / min at an atmosphere of 23°C and 50% RH using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) to measure the 180° peel adhesion of the PSA sheet.
[0381] <<Measurement of shear adhesion>>
[0382] Each adhesive sheet was cut into a length of 20 mm and a width of 20 mm. Under the conditions of an atmosphere of 23°C and 50% RH, one side of the adhesive sheet was attached to the surface of a clean stainless steel plate A (length 100 mm, width 30 mm, thickness 3 mm) that had been subjected to a hairline grinding process with a water-resistant abrasive paper (No. 360) so that the attachment area became 20 mm×20 mm. Next, a clean and smooth stainless steel plate B (length 100 mm, width 30 mm, thickness 3 mm) that had been subjected to a hairline grinding process with a water-resistant abrasive paper (No. 360) was attached to the surface of the adhesive sheet opposite to the surface to which the stainless steel plate A was attached. While applying a load of 5 kg to the stainless steel plate A, the laminated structure of the adhesive sheet and the stainless steel plate B was pressed once by a roller reciprocatingly, and then left to stand for 24 hours under the conditions of an atmosphere of 23°C and 50% RH to serve as a test piece.
[0383] Under the conditions of an atmosphere of 23°C and 50% RH, the stainless steel plate A constituting the test piece was fixed and the stainless steel plate B constituting the test piece was stretched in the shear direction of the adhesive sheet at a stretching speed of 50 mm / min using a Tensilon tensile tester (model: RTF-1210, manufactured by A&D Co., Ltd.) to measure the shear adhesion.
[0384] <<Measurement of splitting adhesive strength>>
[0385] Each adhesive sheet was cut into a length of 20 mm and a width of 20 mm. Under the conditions of an atmosphere of 23°C and 50% RH, one side of the adhesive sheet was attached to the surface of a clean and smooth aluminum plate (alloy number A1050, length 50 mm, width 40 mm, thickness 3 mm) in a manner that the attachment area was 20 mm × 20 mm. Next, a clean and smooth aluminum plate (alloy number A1050, length 50 mm, width 40 mm, thickness 3 mm) was attached to the surface of the adhesive sheet opposite to the surface on which the aluminum plate was attached. While applying a load of 5 kg to the laminated structure of the two aluminum plates and the adhesive sheet, a roller was reciprocated and pressed once to make it pressed together, and then it was left to stand for 24 hours under the conditions of an atmosphere of 23°C and 50% RH to serve as a test piece.
[0386] Under the conditions of an atmosphere of 23°C and 50% RH, with the aluminum plate A constituting the above-mentioned test piece fixed, the aluminum plate B constituting the above-mentioned test piece was stretched along the tearing direction (thickness direction) of the adhesive sheet at a tension rate of 50 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.) to measure the tearing adhesion strength.
[0387] [Table 1]
[0388]
[0389] *1: The amount of filler particles added refers to the amount of filler particles added relative to 100 parts by weight of the adhesive composition (parts by weight)
[0390] [Table 2]
[0391]
[0392] 1: The amount of filler particles added indicates the amount of filler particles added (parts by weight) relative to 100 parts by weight of the adhesive composition.
[0393] (Test Examples 1 to 11)
[0394] The adhesive sheets (1) to (11) of Manufacturing Examples 1 to 11 were cut into pieces with a width of 10 mm and a length of 60 mm, respectively. Fig. 6A As shown, one surface 41a of the adhesive sheet 41 is attached to a clean and smooth aluminum plate 42 (alloy number A1050, length 50mm, width 40mm, thickness 3mm) in a straight line. Next, the other surface 41b of the adhesive sheet 41 is attached to a clean and smooth acrylic plate 43 (length 40mm, width 40mm, thickness 3mm, Acrylite L, color: colorless, manufactured by MITSUBISHI RAYON Co., Ltd.). At this time, the two ends (first gripping portion A and second gripping portion B) of the adhesive sheet 41 in the longitudinal direction (extension direction) are attached in a state where the width and length of the acrylic plate 43 are exposed from both ends of the acrylic plate 43, respectively. Next, the laminated structure of the aluminum plate 42, the adhesive sheet 41 and the acrylic plate 43 is pressed once by a roller while applying a load of 5kg, and then left to stand for 3 days under the conditions of an atmosphere of 23°C and 50%RH.
[0395] The pressure-sensitive adhesive sheets used in Test Examples 1 to 11 are shown in the following Table 3. In addition, in the following Table 3, the attachment method is indicated as "X".
[0396] (Comparative Test Examples 1 to 11)
[0397] The adhesive sheets (1) to (11) of Manufacturing Examples 1 to 11 were cut into pieces with a width of 10 mm and a length of 70 mm, respectively. Figure 6C As shown, one surface 44a of the adhesive sheet 44 is attached to a clean and smooth aluminum plate 42 (alloy number A1050, length 50mm, width 40mm, thickness 3mm) in a straight line. Next, the other surface 44b of the adhesive sheet 44 is attached to a clean and smooth acrylic plate 43 (length 40mm, width 40mm, thickness 3mm, Acrylite L, color tone: colorless, manufactured by MITSUBISHI RAYON Co., Ltd.). At this time, one end (grip portion A') of the adhesive sheet 44 in the longitudinal direction (extension direction) is attached from one end of the acrylic plate 43 in a state where a width of 10mm and a length of 10mm are exposed. Next, a load of 5kg is applied to the laminated structure of the aluminum plate 42, the adhesive sheet 44 and the acrylic plate 43, and the laminated structure is pressed once by a roller reciprocatingly, and then left to stand for 3 days under the conditions of an atmosphere of 23°C and 50%RH.
[0398] The pressure-sensitive adhesive sheets used in Comparative Test Examples 1 to 11 are shown in the following Table 3. In addition, in the following Table 3, the attachment method is indicated as "Y".
[0399] <<Evaluation 1 of removability>>
[0400] The removability in the horizontal direction was evaluated for each of the laminate structures of Test Examples 1 to 11 and Comparative Test Examples 1 to 11 by the following method.
[0401] The first gripping portion A and the second gripping portion B of each of the adhesive sheets used in Test Examples 1 to 11 and the gripping portion A' of each of the adhesive sheets used in Comparative Test Examples 1 to 11 were respectively placed in an atmosphere of 23° C. and 50% RH and 180° (horizontal direction) ( Fig. 6A The stretching direction p or Figure 6C The tensile test was performed by stretching the sample at a speed of 300 mm / min using a Tensilon tensile testing machine (model: RTF-1210, manufactured by A&D Co., Ltd.). The elongation peel test was performed 5 times (n=5) in the horizontal direction and 5 times (n=5) in the vertical direction, for a total of 10 times. It should be noted that in the case of the attachment method X of Test Examples 1 to 11, after the stretch peeling from either the first holding part A or the second holding part B, the stretch peeling from the other was regarded as 1 test (n=1).
[0402] In the stretch peel test, the residual degree of the adhesive on the adherend (acrylic plate) after the adhesive sheet is peeled off is visually confirmed and evaluated based on the following evaluation criteria. In addition, the rupture of the adhesive sheet during the stretch peeling and the disassembly of the aluminum plate and the acrylic plate are evaluated based on the following evaluation criteria. The evaluation results are shown in the following Table 3.
[0403] [Evaluation criteria for adhesive residue]
[0404] ○: No adhesive residue
[0405] ×: There is adhesive residue
[0406] In addition, in the evaluation criteria of the residual adhesive, "○" means that there is no problem in use.
[0407] It should be noted that, as an example of the degree of residual adhesive in the above-mentioned elongation peeling test, the appearance of the acrylic plate after horizontal stretching and peeling of Test Example 1 is shown in FIG. Fig. 7A The appearance of the acrylic plate after horizontal stretching and peeling of Comparative Test Example 1 is shown in Figure 7B .exist Fig. 7A In the figure, "410" indicates the part to which the adhesive sheet is attached, and "p" indicates the stretching direction of the adhesive sheet. Figure 7B In the figure, "440" indicates the part where the adhesive sheet is attached, and "p" indicates the stretching direction of the adhesive sheet. According to the results, when the adhesive sheet is attached in the attachment method X, no adhesive residue is left, whereas when the adhesive sheet is attached in the attachment method Y, obvious residue of the adhesive sheet is confirmed.
[0408] [Evaluation criteria for cracks]
[0409] ◎: The number of ruptures is 0
[0410] ○: The number of ruptures is 1 to 2 times
[0411] △: The number of ruptures is 3 to 4 times
[0412] ×: The number of ruptures is 5
[0413] In addition, in the evaluation criteria of cracking, "○" and "◎" indicate that there is no problem in use.
[0414] [Evaluation criteria for disassembly]
[0415] ◎: The number of times it can be disassembled is 5
[0416] ○: The number of times that the system can be disassembled is 3 to 4 times
[0417] △: The number of times that it can be disassembled is 1 to 2 times
[0418] ×: The number of times that can be disassembled is 5
[0419] In addition, in the evaluation criteria of disassembly, "○" and "◎" indicate that there is no problem in use.
[0420] [Table 3]
[0421]
[0422] According to the results in Table 3, in the case where the attachment method of test examples 1 to 11 is X, there is no contamination caused by the adhesive after peeling, and even if it breaks in the middle of the elongated peeling from one end (the first holding part), it can be peeled off from the other end (the second holding part) to the end. On the other hand, in the case where the attachment method of comparative test examples 1 to 11 is Y, even if it can be stretched and peeled, the adhesive remains on the adherend, and in the case of breaking in the middle of the elongated peeling from one end, it cannot be peeled off to the end, and the aluminum plate and the acrylic plate cannot be disassembled.
[0423] <<Evaluation 2 of removability>>
[0424] For each of the laminate structures of Test Examples 1 to 11, the removability in the vertical direction was evaluated by the following method.
[0425] In the above-mentioned <<Evaluation 1 of Removability>>, the stretching conditions of the first gripping portion A and the second gripping portion B of each of the adhesive sheets used in Test Examples 1 to 11 were changed from the 180° direction (horizontal direction) ( Fig. 6A The stretching direction p) is changed to a direction at 90° (vertical direction) relative to the attachment surface of the adhesive sheet ( Figure 6B The adhesive sheet was peeled off from the adherend (acrylic sheet) and the adhesive sheet was peeled off from the adherend (acrylic sheet) and the adhesive sheet was peeled off from the adherend (acrylic sheet). The results of the evaluation are shown in Table 4 below.
[0426] [Table 4]
[0427]
[0428] The results in Table 4 show that even when the PSA sheets (2) to (11) of Test Examples 2 to 11 were pulled and peeled in a 90° direction (perpendicular direction) relative to the attached surface of the PSA sheet, there was no contamination due to the PSA after peeling.
[0429] As aspects of the present invention, for example, the following aspects can be mentioned.
[0430] <1> An electronic component, characterized in that it includes an adhesive sheet, wherein one surface of the adhesive sheet is attached to a first attachment object in a manner in which at least a portion of the surface is linear, and the other surface of the adhesive sheet is attached to a second attachment object, and the adhesive sheet is attached to the second attachment object in a state in which at least two ends are exposed from the second attachment object.
[0431] <2> The electronic component according to <1> above, wherein at least one of the first attachment target and the second attachment target is a recycling component.
[0432] <3> The electronic component according to any one of <1> to <2>, wherein the recycled component is at least one of display glass and a battery.
[0433] <4> An electronic component according to any one of <1> to <3> above, wherein, when the width of the attachment area of the adhesive sheet in the electronic component is set to X (cm) and the length of the attachment area is set to Y (cm), the ratio of the width of the attachment area to the length of the attachment area (X / Y) is 1 / 100000 to 1 / 1.
[0434] Industrial Applicability
[0435] The electronic component is provided with an adhesive sheet, which can be quickly peeled off without contamination caused by the adhesive after peeling off. Even if the adhesive sheet is broken in the middle of being peeled off from one end, it can be peeled off from the other end to the end, and has appropriate adhesive force when used. Therefore, it can be used as a wide range of electronic components, regardless of the size of the electronic components, such as large electronic devices such as thin-film televisions, home appliances, and OA equipment, and components constituting the same, and small electronic devices such as portable electronic terminals, cameras, and personal computers, and components constituting the same.
[0436] Description of Reference Numerals
[0437] 1: Handle tab
[0438] 2: Bonding area
[0439] 3: terminal part
[0440] 4: First bonding area
[0441] 5: Second bonding area
[0442] 6: The third bonding area
[0443] 7: Front end
[0444] 21: Adhesive sheet
[0445] 21a: One surface of the adhesive sheet 21
[0446] 21b: The other surface of the adhesive sheet 21
[0447] 22: First attachment object
[0448] 23: Second attachment object
[0449] 31: Adhesive sheet
[0450] 32: Acrylic board
[0451] 33: ABS board
[0452] 34: U-shaped measuring table
[0453] 35: Impact core
[0454] 41: Adhesive sheet
[0455] 41a: One surface of the adhesive sheet 41
[0456] 41b: The other surface of the adhesive sheet 41
[0457] 42: First attachment object
[0458] 43: Second attachment object
[0459] 44: Adhesive sheet
[0460] 61: Adhesive sheet
[0461] 61a: One surface of the adhesive sheet 61
[0462] 61b: The other surface of the adhesive sheet 61
[0463] 62: Rear base
[0464] 63: Battery
[0465] 71: Adhesive sheet
[0466] 71a: One surface of the adhesive sheet 71
[0467] 71b: The other surface of the adhesive sheet 71
[0468] 72: Border
[0469] 73: Display
[0470] 410: Area with adhesive sheet attached
[0471] 440: Area with adhesive sheet attached
[0472] A: First grip
[0473] B: Second grip
[0474] C: The third grip
[0475] D: Fourth grip
[0476] A': grip
[0477] p: stretching direction
Claims
1. An electronic component, characterized in that: A pressure-sensitive adhesive sheet is provided, wherein one surface of the pressure-sensitive adhesive sheet is attached to a first attachment object in a manner that at least a portion of the surface is linear, and the other surface of the pressure-sensitive adhesive sheet is attached to a second attachment object, and the pressure-sensitive adhesive sheet is attached to the second attachment object in a state where at least two ends are exposed from the second attachment object, The stress of the adhesive sheet at 25% elongation is within a range of 0.15 MPa to 2 MPa.
2. An electronic component, characterized in that: A pressure-sensitive adhesive sheet is provided, wherein one surface of the pressure-sensitive adhesive sheet is attached to a first attachment object in a manner that at least a portion of the surface is linear, and the other surface of the pressure-sensitive adhesive sheet is attached to a second attachment object, and the pressure-sensitive adhesive sheet is attached to the second attachment object in a state where at least two ends are exposed from the second attachment object, The 180° peeling adhesion of the adhesive sheet is 15.5 N / 20 mm to 35 N / 20 mm.
3. The electronic component according to claim 1 or 2, wherein: At least one of the first attachment object and the second attachment object is a recycling component.
4. The electronic component according to claim 1 or 2, wherein: The recycled component is at least one of display glass and batteries.
5. The electronic component according to claim 1 or 2, wherein: When the width of the adhesive sheet attached area in the electronic component is X and the length of the attached area is Y, the ratio of the width of the attached area to the length of the attached area, i.e., X / Y, is 1 / 100000 to 1 / 1, wherein the units of X and Y are cm.
6. The electronic component according to claim 1 or 2, wherein: The pressure-sensitive adhesive sheet has at least a pressure-sensitive adhesive layer containing filler particles.
7. The electronic component according to claim 1 or 2, wherein: The splitting adhesion of the adhesive sheet is 80N / 4cm 2 above.
8. The electronic component according to claim 1 or 2, wherein: The end of the adhesive sheet exposed from the second attachment target is a holding portion, and the adhesive surface of the adhesive sheet to be bonded to the second attachment target is adjacent to the holding portion.
9. A method for disassembling an electronic component, characterized in that: The disassembling method is the electronic component disassembling method according to any one of claims 1 to 8, wherein the first attachment object and the second attachment object are disassembled by stretching and peeling the adhesive sheet from at least one gripping portion of the adhesive sheet exposed from the second attachment object.
10. The electronic component disassembly method according to claim 9, characterized in that: The first attachment object and the second attachment object are separated by simultaneously stretching the plurality of gripping portions of the adhesive sheet exposed from the second attachment object to stretch and peel the adhesive sheet; or After a portion of the adhesive sheet is peeled off by stretching any one of the plurality of holding portions of the adhesive sheet exposed from the second attached object, the remaining portion is peeled off by stretching at least one of the holding portions other than the previously stretched holding portion, thereby disassembling the first attached object and the second attached object.
Citation Information
Patent Citations
Adhesive tape and tape substrate used therefor
JP2015124289A
Adhesive film strip and its use
US6680096B1